Biaxially stretched plastic film for optical use, polarizing plate, image display device, and method for selecting biaxially stretched plastic film
By using a biaxial stretched plastic film and adjusting its absorption axis configuration with the polarizer, the problem of black screen of liquid crystal display elements or organic EL elements when wearing polarized glasses is solved, and the mechanical properties of the plastic film are improved.
Patent Information
- Application Number
- CN202510215807.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-30
- Publication Date
- 2025-04-11
AI Technical Summary
Prior Art When using liquid crystal display elements or organic EL elements outdoors, wearing polarized sunglasses or goggles will cause black screen problems, and the uniaxial stretched plastic film is prone to breaking and bending tends to be strong.
A biaxially stretched plastic film is used, and the in-plane phase difference is less than 2500 nm and the deviation of the luminance difference is more than 100. By adjusting the absorption axis of the polarizer and the slow axis configuration of the plastic film, the black screen is eliminated.
Without increasing the in-plane phase difference, the black screen when wearing polarized glasses is effectively suppressed, and the mechanical strength and bending resistance of the plastic film are improved.
Smart Images

Figure CN119805649A_ABST
Abstract
Description
[0001] This application is a divisional application of a Chinese invention patent application with an application date of September 30, 2020, an invention name of “Biaxially stretched plastic film for optical use, polarizing plate, image display device, and method for selecting biaxially stretched plastic film”, and an application number of 202080077484.3 (PCT / JP2020 / 037050). Technical Field
[0002] The present disclosure relates to a biaxially stretched plastic film for optical use, a polarizing plate, an image display device, and a method for selecting a biaxially stretched plastic film. Background Art
[0003] Liquid crystal display elements and organic EL elements are used in various electronic devices to convey information visually. These display elements are not only used indoors, but also have been increasingly used outdoors in recent years due to the popularity of smartphones and digital signage.
[0004] In the case of a liquid crystal display element, the observer sees light that has passed through the polarizer on the light emitting side, and in the case of an organic EL element, the observer sees light that has passed through the polarizer that is provided closer to the observer than the light emitting layer in order to prevent reflection of external light. Therefore, the observer sees polarized light in both the case of a liquid crystal display element and an organic EL element.
[0005] Thus, when the image display device is used outdoors, there is a chance that an observer wearing polarized sunglasses or polarized goggles will receive information based on polarized light. At this time, if the vibration plane of the light that has passed through the polarizer on the observer's side is perpendicular to the absorption axis of the polarizer such as polarized sunglasses or polarized goggles, the light emitted from these image display devices is blocked by the polarized sunglasses or polarized goggles, and the observer is in a so-called black-out state where the liquid crystal display element appears to be completely dark. Polarized sunglasses or polarized goggles are sometimes worn not only outdoors but also indoors, so it is important to eliminate the black-out state.
[0006] In order to eliminate the black screen, a method is disclosed in which the angle between the absorption axis of the polarizer of the polarizing plate and the slow axis of the polymer film is set to about 45 degrees using a polymer film (Patent Document 1).
[0007] Patent document 1 discloses a liquid crystal display device, which can eliminate the black screen when observing with polarized sunglasses or polarized goggles, etc. by setting the light source of the image display device to a specific white light source, increasing the in-plane phase difference (Re, delay) of the stretched plastic film to above 3000nm and below 30000nm, and configuring the absorption axis of the polarizer and the slow axis of the stretched plastic film at approximately 45 degrees.
[0008] However, the method of Patent Document 1 requires the use of a stretched plastic film with a large in-plane phase difference. Moreover, a stretched plastic film with a large in-plane phase difference is usually uniaxially stretched, so it is easy to break in the stretching direction and has a strong tendency to bend in the direction perpendicular to the stretching direction.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-107198 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The present disclosure aims to provide a biaxially stretched plastic film for optics, a polarizing plate, and an image display device capable of suppressing a black screen when observing with polarized sunglasses or polarized goggles without increasing the in-plane phase difference.
[0014] Means for solving problems
[0015] As a result of intensive studies, the present inventors have found that the above-mentioned problems can be solved by setting the "variation 3σ of brightness difference" to be described later to 100 or more and setting the in-plane phase difference (Re) to 2500 nm or less.
[0016] The present disclosure provides the following biaxially stretched optical plastic film, a functional film, a polarizing plate, and an image display device using the biaxially stretched optical plastic film, and a method for selecting the biaxially stretched optical plastic film.
[0017] [1] A biaxially stretched plastic film for optical use, wherein:
[0018] The biaxially stretched plastic film for optical use has a region satisfying <Condition 1> and <Condition 2>,
[0019] <Condition 1>
[0020] The luminance difference (L1.n-L2.n) between the luminance obtained in the following measurement 1 and the luminance obtained in the following measurement 2 is calculated at 100 measurement points, and the "luminance difference deviation 3σ" calculated from the luminance difference at the 100 measurement points is 100 or more,
[0021] Measurement 1
[0022] A first measurement sample is prepared in which a first polarizer, an optical biaxially stretched plastic film, and a second polarizer are arranged in this order on a surface light source. In the first measurement sample, the direction of the slow axis of the optical biaxially stretched plastic film is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer, and the absorption axis of the second polarizer is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer.
[0023] The surface light source of the first measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at measurement points of 100×100 set at equal intervals in the vertical and horizontal directions in an arbitrary first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L1.1, the brightness of the 100th measurement point is defined as L1.100, and the brightness of the nth measurement point is defined as L1.n,
[0024] Measurement 2
[0025] A second measurement sample is prepared in which the first polarizer and the second polarizer are arranged in this order on the same surface light source as the measurement 1, wherein in the second measurement sample, the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer.
[0026] The surface light source of the second measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at 100×100 measurement points set at equal intervals in the vertical and horizontal directions in an area roughly consistent with the first measurement area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L2.1, the brightness of the 100th measurement point is defined as L2.100, and the brightness of the nth measurement point is defined as L2.n;
[0027] <Condition 2>
[0028] The in-plane retardation (Re) is 2500 nm or less.
[0029] [2] The biaxially stretched plastic film for optical use according to [1], wherein the in-plane retardation relative to the retardation in the thickness direction is 0.10 or less.
[0030] [3] The biaxially stretched optical plastic film according to [1] or [2], wherein the biaxially stretched optical plastic film has a film thickness of 20 μm to 200 μm.
[0031] [4] A functional film comprising the biaxially stretched plastic film for optical use according to any one of [1] to [3], wherein the functional layer is provided on one surface of the biaxially stretched plastic film.
[0032] [5] A polarizing plate comprising a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is a biaxially stretched plastic film for optical use as described in any one of [1] to [3].
[0033] [6] An image display device comprising a display element and a plastic film disposed on a light emitting surface side of the display element, wherein the plastic film is the biaxially stretched plastic film for optical use according to any one of [1] to [3].
[0034] [7] The image display device according to [6], wherein a polarizer is provided between the display element and the plastic film.
[0035] [8] The image display device according to [6] or [7], further comprising a functional layer on the side of the biaxially stretched optical plastic film opposite to the display element.
[0036] [9] An image display device comprising a first polarizer and an optical biaxially stretched plastic film on a light emitting surface of a display element, wherein:
[0037] The image display device is configured such that the direction of the slow axis of the optical biaxially stretched plastic film is substantially perpendicular to the direction of the absorption axis of the first polarizer, and the optical biaxially stretched plastic film has a region satisfying <Condition 1B> and <Condition 2B>,
[0038] <Condition 1B>
[0039] The luminance difference (L1.n-L2.n) between the luminance obtained in the following measurement 1B and the luminance obtained in the following measurement 2B is calculated at 100 measurement points, and the "luminance difference deviation 3σ" calculated from the luminance difference at the 100 measurement points is 100 or more,
[0040] Measurement 1B
[0041] A 1B measurement sample is prepared in which the first polarizer, the optical biaxially stretched plastic film, and the second polarizer are arranged in this order on the display element, wherein in the 1B measurement sample, the slow axis of the optical biaxially stretched plastic film is arranged to be approximately perpendicular to the absorption axis of the first polarizer, and the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer.
[0042] The display element of the 1B measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at measurement points of 100×100 set at equal intervals in the vertical and horizontal directions in an arbitrary first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L1.1, the brightness of the 100th measurement point is defined as L1.100, and the brightness of the nth measurement point is defined as L1.n,
[0043] Measurement 2B
[0044] A measurement sample 2B is prepared on the same display element as the measurement sample 1B, in which the first polarizer and the second polarizer are arranged in this order. In the measurement sample 2B, the absorption axis of the second polarizer is arranged to be substantially perpendicular to the absorption axis of the first polarizer.
[0045] The display element of the 2B measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at 100×100 measurement points set at equal intervals in the vertical and horizontal directions in an area substantially consistent with the first measurement area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L2.1, the brightness of the 100th measurement point is defined as L2.100, and the brightness of the nth measurement point is defined as L2.n;
[0046] <Condition 2B>
[0047] The in-plane retardation (Re) is 2500 nm or less.
[0048]
[10] A method for selecting a biaxially stretched plastic film for optical use, which is a method for selecting a biaxially stretched plastic film for an image display device having a biaxially stretched plastic film for optical use on the surface on the light emitting surface side of a display element, wherein a region satisfying <Condition 1> and <Condition 2> is used as a judgment condition, and a biaxially stretched plastic film satisfying the judgment condition is selected as the biaxially stretched plastic film for optical use.
[0049] Effects of the Invention
[0050] The optical biaxially stretched plastic film, the functional film using the optical biaxially stretched plastic film, the polarizing plate and the image display device disclosed herein can suppress black screen when observing with polarized sunglasses or polarized goggles without increasing the in-plane phase difference. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1This is a schematic diagram showing a measurement method when calculating "3σ of the luminance difference deviation".
[0052] Figure 2 This is a schematic diagram showing a measurement method when calculating "3σ of the luminance difference deviation".
[0053] Figure 3 It is a schematic diagram showing an example of the measurement area when calculating the "deviation 3σ of the luminance difference".
[0054] Figure 4 is a schematic diagram showing an example of a measurement area.
[0055] Figure 5 This is a top view for explaining five measurement points in conditions 2 to 4.
[0056] Figure 6 It is a figure which shows schematically the state of a continuous folding test.
[0057] Figure 7 This is a schematic diagram showing that the biaxially stretched optical plastic film disclosed in the present invention is applied to a liquid crystal display element.
[0058] Figure 8 This is a schematic diagram showing that the biaxially stretched plastic film for optical use disclosed in the present invention is applied to an organic EL element.
[0059] Fig. 9 is used to explain condition A [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )]. DETAILED DESCRIPTION
[0060] Hereinafter, embodiments of the present disclosure will be described.
[0061] [Biaxially stretched plastic film for optical use]
[0062] The biaxially stretched plastic film for optical use of the present disclosure has a region (hereinafter, sometimes also referred to as a “measurement region”) satisfying the following conditions 1 and 2.
[0063] <About measurement conditions>
[0064] <Condition 1>
[0065] The "deviation 3σ of brightness difference" in condition 1 is obtained using L1.n obtained in the following measurement 1 and L2.n obtained in measurement 2. In addition, in this specification, 3σ refers to 3σ used in statistics. 3σ in statistics means that the measurement data exists in the area of ±3σ with a probability of 99.7% relative to 100% of the area of the normal distribution curve obtained from the histogram. That is, in condition 1, it means that the area of ±3σ of the histogram of brightness difference of 100 measurement points is greater than 100. In addition, in this specification, "brightness" refers to the energy of light detected by the measurement step described later, and is a dimensionless value.
[0066] Measurement 1
[0067] use Figure 1 , Figure 3 and Figure 4 A method for measuring the luminance L1.n at the nth measurement point will be described.
[0068] like Figure 1 As shown, for the optical biaxially stretched plastic film (10) of the present invention, a surface light source (1), a first polarizer (2), an optical biaxially stretched plastic film (10), and a second polarizer (3) are stacked in this order, and this is referred to as a first measurement sample (4).
[0069] The first measurement sample is arranged in such a manner that the direction of the slow axis of the optical biaxially stretched plastic film is substantially perpendicular to the direction of the absorption axis of the first polarizer, and the absorption axis of the second polarizer is substantially perpendicular to the direction of the absorption axis of the first polarizer. In this specification, unless otherwise specified, substantially perpendicular means within 90 degrees ± 5 degrees, preferably within 90 degrees ± 3 degrees, and more preferably within 90 degrees ± 1 degree.
[0070] Next, an imaging luminance meter 20 is set at a position 750 mm from the surface of the surface light source. Furthermore, the second polarizer may be disposed just in front of the imaging luminance meter 20. That is, the optical biaxially stretched plastic film and the second polarizer may not be in contact with each other.
[0071] Next, any area on the second polarizer is used as the measurement area of measurement 1, such as Figure 3As shown, a total of 10,000 measurement points of 100×100 in length and width are evenly set in the measurement area. The measurement area of measurement 1 is called the "first measurement area". The arbitrary area is preferably 100mm×100mm, but in the case of a small display element such as a mobile device, it can also be set to a narrower area. Select one column of any row in the horizontal 100, and define the area from the first measurement point to the 100th measurement point by setting the leftmost cell as the first measurement point and the rightmost cell as the 100th measurement point. Use the aforementioned imaging luminance meter to measure the luminance at each measurement point. Set the luminance of the first measurement point to L1.1, the luminance of the 100th measurement point to L1.100, and the luminance of the nth measurement point in the first measurement sample to L1.n.
[0072] The vertical and horizontal measurement points of 100×100 are as follows Figure 3 As shown in the figure, the longitudinal and transverse directions of the first measurement sample are used as the reference. Similarly, the longitudinal and transverse directions of the measurement points of the 100×100 vertical and horizontal directions of measurement 2 are used as the reference of the longitudinal and transverse directions of the second measurement sample. If the top view shapes of the first measurement sample and the second measurement sample are rectangular or square, it is easy to identify the longitudinal and transverse directions. In addition, there is no need to distinguish between the longitudinal and transverse directions.
[0073] When the top view shapes of the first and second measurement samples are shapes other than rectangles or squares (circles, triangles, etc.), it is sufficient to draw a rectangle or square with the largest area that does not protrude from the outer frame shapes of these samples and determine the longitudinal or transverse direction based on the drawn rectangle or square.
[0074] Also, the luminance is measured in a dark room.
[0075] The first polarizer is preferably configured in such a way that the absorption axis of the first polarizer is approximately parallel to the horizontal or vertical direction of the surface light source. In this specification, the term "approximately parallel" means that the difference between the absorption axis of the polarizer and the horizontal or vertical direction of the surface light source is within ±5 degrees, preferably within ±3 degrees, and more preferably within ±1 degree.
[0076] The horizontal and vertical determination of the surface light source is based on the horizontal and vertical determination of the first and second measurement samples. The configuration of the first polarizer in a manner that the angle between the absorption axis of the first polarizer and the left-right direction or the up-down direction of the surface light source is roughly parallel is made in consideration of the following situation: the polarizer on the light emitting surface side of a commonly used image display device is configured in this way.
[0077] Furthermore, in measurement 1, a measurement point whose brightness variation with respect to an adjacent measurement point exceeds 30% is excluded from the measurement result as a measurement point due to a local defect of a component constituting the first measurement sample. In the case of such an abnormal point, 3σ of condition 1 is calculated based on points other than the abnormal point. The same applies to measurement 2 described later. In addition, regarding adjacent measurement points, for example, Figure 3 In the case of the first measuring point, it is the second measuring point, and in the case of the fifth measuring point, it is the fourth and sixth measuring points.
[0078] The number of luminance measurement points used in calculating the "3σ deviation of luminance difference" is preferably 10 or more, more preferably 20 or more, more preferably 30 or more, more preferably 40 or more, more preferably 50 or more, more preferably 70 or more, and more preferably 90 or more. If the number of luminance values used in the calculation is small, the properties of the first measurement sample cannot be reflected, which is not preferred.
[0079] The above number of measurement points is particularly preferred in a small display device.
[0080] On the other hand, in the case of a large display device of 20 inches or more (or even 50 inches or more), in order to measure the deviation well, the number of measurement points is preferably 80 or more, and more preferably 90 or more.
[0081] The upper limit of the number of measurement points of luminance is 100. The number of measurement points of luminance is most preferably 100, but is preferably 80 or more in order to fully reflect the properties of the first measurement sample.
[0082] For example, there are cases where the biaxially stretched plastic film for optical use is in the form of a sheet (see Figure 4 ); and in a roll-like form. The measurement of condition 1 can directly use a sheet or roll-like biaxially stretched plastic film for optical use, but in case of ease of handling, or in case the biaxially stretched plastic film for optical use is too large to be placed in the measuring device, it can also be cut into a size of more than 100 mm in length × more than 100 mm in width (hereinafter referred to as a measurement sample), and the 100 mm in length × 100 mm in width area on the inside of its contour by more than 1 mm in height, left, right, and above is used as the measurement area. The reason for measuring the area inside the sample is to take into account the following situation: when the sample is cut, stress is easily applied to the edge of the plastic film, so the optical axis near the edge of the sample is sometimes deformed. Figure 4 , an example in which first to third samples ( 21 , 22 , 23 ) were cut out from a sheet-like biaxially stretched plastic film 10 for optical use is shown.
[0083] When cutting out and using, it can be cut out from any position of the optical biaxially stretched plastic film, but when the longitudinal and transverse directions of the sheet and the roll can be confirmed, the sample is cut out along the confirmed longitudinal and transverse directions. For example, in the case of a roll, the conveying direction (MD direction) of the roll can be regarded as the longitudinal direction, and the width direction (TD direction) of the roll can be regarded as the transverse direction. In addition, when the conveying direction and width direction of the sheet can be confirmed, the conveying direction can be regarded as the longitudinal direction and the width direction can be regarded as the transverse direction. In the case where it is difficult to confirm the conveying direction and width direction of the sheet, if the sheet is a rectangle or a square, it is sufficient to confirm the longitudinal and transverse directions through the four sides that constitute the rectangle or the square. In the case where it is difficult to confirm the conveying direction and width direction of the sheet, if the sheet is a shape other than a rectangle or a square (circle, triangle, etc.), it is sufficient to draw a rectangle or square that does not protrude from the outer frame shape of the sheet and has the largest area and confirm the longitudinal and transverse directions through the sides of the drawn rectangle or square. In the case of a sheet-like biaxially stretched optical plastic film, the sample is preferably cut out from near the center, and in the case of a roll-like biaxially stretched optical plastic film, the sample is preferably cut out from near the center in the width direction of the roll.
[0084] The above-described embodiment of the sample under condition 1 can be applied to the embodiment of the sample under condition 2 described later (however, in condition 2, the size of the sample is 100 mm×100 mm).
[0085] Furthermore, when a biaxially stretched optical plastic film is incorporated into a commercially available image display device, the image display device can be disassembled and the biaxially stretched optical plastic film can be removed by peeling it off from the laminated body arranged on the display element, and the removed biaxially stretched optical plastic film can be evaluated to see whether it satisfies conditions 1 and 2.
[0086] The luminance is measured as follows in Measurement 1 and Measurement 2. As described above, the luminance in Measurement 1 and Measurement 2 refers to the energy of light detected by the following measurement steps and is a dimensionless value.
[0087] The measurement atmosphere in measurement 1 and measurement 2 was: temperature 23°C ± 5°C, relative humidity 40% RH or more and 65% RH or less. In addition, before performing measurement 1 and measurement 2, the first measurement sample and the second measurement sample were left to stand in the atmosphere for more than 30 minutes.
[0088] 《Measurement steps for measurement 1》
[0089] The surface light source of the first measurement sample was made to display white.
[0090] As a measuring device, a device with a product number of "Prometric PM1423-1, imaging luminance meter, CCD resolution: 1536×1024" manufactured by Cybernet Corporation was used. Figure 1 The first measurement sample and the imaging luminance meter are set at a positional relationship of . The distance between the camera and the surface light source is set to 750 mm.
[0091] Next, the following “settings before measurement” and “adjustment of exposure time” were performed, and then the following “measurement and analysis” was performed. The measurement was performed in a darkroom environment.
[0092] <Settings before measurement>
[0093] (1) Connect the imaging luminance meter to a personal computer and start the attached software (RADIANT IMAGING Prometric 9.1 Version 9.1.32) of the imaging luminance meter in the personal computer.
[0094] (2) When the software is started, the CCD temperature in the imaging luminance meter is automatically adjusted to blue display (-10°C). Wait until the CCD temperature stabilizes at -10°C.
[0095] (3) In the "Measurement Settings" of the software, specify "Color, 1x1 binning".
[0096] (4) Set the lens aperture dial to 1.8 and bring the second polarizer into focus.
[0097] <Adjustment of exposure time>
[0098] Implement the "Exposure Time Adjustment" of the software. Specifically, press "Adjust" in the order of Y (green), X (red), and Z (blue), and then save. Adjust the exposure time every time you measure a sample.
[0099] <Measurement and Analysis>
[0100] Select "Focus mode" from the tool bar and confirm that the measurement target area is reflected in the focus mode image.
[0101] Press "Measure" to start the measurement and save the measurement results.
[0102] Select "Tools" and "Measurement Data Processing" from the toolbar. Next, select "Cut Range" from the "Select Processing Content" drop-down menu. Next, specify a range equivalent to 100mm×100mm of the sample and save it. The saved data is referred to as "Saved Data 1". (In addition, in the case of a small display element such as a mobile device, a range smaller than 100mm×100mm can also be specified. For example, in the case of a small display element, a range of 30mm×100mm, 30mm×70mm, 30mm×50mm, 30mm×30mm, etc. can also be specified. In addition, in the case of a small display element, the range can be specified according to the size and shape corresponding to the shape of the element.)
[0103] Open saved data 1. Next, select "Tools" and "Export of measurement data" from the tool bar. Next, select "Brightness" as the data type, set the resolution to "X: 100, Y: 100", and set the output format to "XY Table", and export the Excel data.
[0104] Through the above steps, the brightness data of 100×100 measurement points are obtained. By extracting 100 points in any horizontal row from the measurement results, we can obtain Figure 3 The 100-point luminance data (L1.n. luminance of measurement 1) are shown.
[0105] 《Measurement steps for measurement 2》
[0106] In the measurement step of measurement 1, if "the first measurement sample" and "L1.n. the brightness of measurement 1" are replaced with "the second measurement sample" and "L2.n. the brightness of measurement 2", it becomes the measurement step of measurement 2.
[0107] Measurement 2
[0108] use Figure 2 , Figure 3 and Figure 4 A method for measuring the luminance L2.n at the nth measurement point will be described.
[0109] The second measurement sample obtained by removing the optical biaxially stretched plastic film from the first measurement sample of measurement 1 is used, and the brightness is measured in the same manner except that the optical biaxially stretched plastic film is removed. The second measurement area, which is the measurement area of measurement 2, is made substantially consistent with the first measurement area, which is the measurement area of measurement 1. Substantially consistent in this specification means that the deviation of the measurement area is within 0.5 mm, preferably within 0.3 mm, and more preferably within 0.1 mm.
[0110] Use Figure 3In the case described in measurement 1, 100 measurement points are set and the luminance is measured at each point. The first measurement point in the second measurement sample is roughly the same as the first measurement point in the first measurement sample, and the luminance is set to L2.1. The 100th measurement point in the second measurement sample is roughly the same as the 100th measurement point in the first measurement sample, and the luminance is set to L2.100. The luminance of the nth measurement point in the second measurement sample is set to L2.n.
[0111] Furthermore, the horizontal column involved in L2.n of measurement 2 is made consistent with the arbitrary horizontal column involved in L1.n of measurement 1. For example, when the arbitrary horizontal column involved in L1.n of measurement 1 is the horizontal column of the 50th row, the arbitrary horizontal column involved in L2.n of measurement 2 is also set to the horizontal column of the 50th row.
[0112] The difference between the brightness at the first measurement point obtained in measurement 1 and the brightness at the first measurement point obtained in measurement 2 is calculated. Similarly, the brightness difference is calculated for each of the 100 points up to the 100th measurement point, and the "brightness difference deviation 3σ" is calculated from the brightness differences of the 100 points.
[0113] For confirmation, the surface light source (1), the first polarizer (2), and the second polarizer (3) are sequentially overlapped in measurement 2. At this time, the second polarizer is arranged so that the absorption axis direction is substantially perpendicular to the absorption axis direction of the first polarizer.
[0114] Furthermore, regarding the upper limit and the lower limit in the present application, the values described may be appropriately combined to express a range with these being the maximum value and the minimum value.
[0115] Condition 1 stipulates that "brightness difference deviation 3σ" is 100 or more.
[0116] Since L1.n and L2.n are values including characteristics of the backlight and environmental factors, in Condition 1 of the present disclosure, the “luminance difference deviation 3σ” is calculated using the luminance difference (L1.n-L2.n) which is the difference between L1.n and L2.n.
[0117] If the "brightness difference deviation 3σ" is greater than 100, a black screen will not be generated, or its effect will be weak, and information on a smartphone using an optical biaxially stretched plastic film can be read while wearing polarized sunglasses or polarized goggles. Therefore, the lower limit of the "brightness difference deviation 3σ" needs to be greater than 100, preferably greater than 105, and more preferably greater than 110. On the other hand, if the "brightness difference deviation 3σ" is too large, undesirable conditions such as a decrease in mechanical strength are likely to occur. In addition, wrinkles of the optical biaxially stretched plastic film caused by humidity, etc., and rainbow unevenness caused by deformation may sometimes occur. Therefore, the upper limit is preferably less than 800, more preferably less than 600, more preferably less than 500, and more preferably less than 450.
[0118] By satisfying conditions 3 and 4 described later, condition 1 can be easily satisfied.
[0119] Regarding the preferred range of the deviation 3σ of the luminance difference under condition 1, for example, there can be cited greater than 100 and less than 800, greater than 100 and less than 600, greater than 100 and less than 500, greater than 100 and less than 450, greater than 105 and less than 800, greater than 105 and less than 600, greater than 105 and less than 500, greater than 105 and less than 450, greater than 110 and less than 800, greater than 110 and less than 600, greater than 110 and less than 500, and greater than 110 and less than 450.
[0120] The deviation 3σ of the brightness difference of condition 1 is calculated based on any horizontal column among the 100 columns. In the present embodiment, the columns satisfying condition 1 are preferably 50 or more columns among the 100 columns, more preferably 70 or more columns, more preferably 90 or more columns, more preferably 95 or more columns, and more preferably 100 columns.
[0121] The lower limit of L1.n used in the calculation of "brightness difference deviation 3σ" is preferably 80 or more, more preferably 100 or more. The upper limit of L1.n is preferably 1200 or less, more preferably 1000 or less, and further preferably 500 or less.
[0122] Preferred ranges of L1.n include 80 to 1200, 100 to 1000, 80 to 500, 100 to 1200, 100 to 1000, and 100 to 500.
[0123] The lower limit of the average value of 100 points of L1.n is preferably 150 or more, more preferably 200 or more, and further preferably 250 or more, and the upper limit is preferably 800 or less, more preferably 600 or less, and further preferably 500 or less. By setting the average value of 100 points of L1.n to the above range, condition 1 can be easily satisfied.
[0124] The lower limit of L2.n used in the calculation of "brightness difference deviation 3σ" is preferably 20 or more, more preferably 30 or more. The upper limit of L2.n is preferably 600 or less, more preferably 500 or less, and further preferably 300 or less.
[0125] Preferred ranges of L2.n include 20 to 600, 30 to 600, 20 to 500, 30 to 500, 20 to 300, and 30 to 300.
[0126] The lower limit of the average value of 100 points of L2.n is preferably 20 or more, more preferably 30 or more, and the upper limit is preferably 600 or less, more preferably 500 or less, and further preferably 300 or less. By setting the average value of 100 points of L2.n to the above range, condition 1 can be easily satisfied.
[0127] The surface light source is not particularly limited as long as it can display white. In addition, the lower limit of the color temperature when the surface light source displays white is preferably 5000K or more, more preferably 6000K or more, and further preferably 6500K or more, and the upper limit is preferably 13000K or less, more preferably 12000K or less, and further preferably 11000K or less. By setting the color temperature of the white display to the above range, the measurement results can be easily homogenized.
[0128] Regarding the surface light source, for example, a commonly used image display device such as a liquid crystal display device and an organic EL display device can be used. However, in the case where the image display device has an observation side polarizer on the display element, the portion other than the observation side polarizer is regarded as the surface light source. This is because the observation side polarizer can become the first polarizer. In addition, in the case where the surface light source is a liquid crystal display device, as the backlight source of the liquid crystal display device, a backlight source using quantum dots and a backlight source using white light emitting diodes can be cited.
[0129] The first polarizer is preferably not a polarizer disposed on a display element of a commercially available image display device, but is prepared separately. Furthermore, when a polarizer disposed on a display element of a commercially available image display device is taken out in a good state, the taken out polarizer can be used as the first polarizer.
[0130] Regarding the brightness of the transmitted light emitted from the first polarizer side when the first polarizer is arranged on the surface light source, as the average value of 100 points in the measurement area excluding the second polarizer in measurement 2, the lower limit is preferably 15000 or more, more preferably 17000 or more, more preferably 18000 or more, more preferably 20000 or more, and the upper limit is preferably 60000 or less, more preferably 50000 or less, more preferably 40000 or less, and more preferably 38000 or less. If it is within this range, the "deviation 3σ of brightness difference" can be calculated with high reproducibility.
[0131] Preferred ranges of the brightness of the transmitted light include 15,000 to 60,000, 15,000 to 50,000, 15,000 to 40,000, 15,000 to 38,000, 17,000 to 60,000, 17,000 to 50,000, 17,000 to 40,000, 17,000 to 38,000, 18,000 to 60,000, 18,000 to 50,000, 18,000 to 40,000, 18,000 to 38,000, 20,000 to 60,000, 20,000 to 50,000, 20,000 to 40,000, and 20,000 to 38,000.
[0132] Regarding 3σ of the brightness of the transmitted light emitted from the first polarizer side when the first polarizer is arranged on the surface light source, as a value calculated based on 100 points in the measurement area after removing the second polarizer from measurement 2, the lower limit is preferably 1000 or more, more preferably 1300 or more, more preferably 1500 or more, and the upper limit is more preferably 10000 or less, more preferably 8000 or less, and more preferably 70000 or less. As described above, the "deviation 3σ of brightness difference" is obtained by taking a difference to exclude the influence of the surface light source, etc., but by setting the 3σ of the brightness of the transmitted light to the above range, the "deviation 3σ of brightness difference" can be calculated with high reproducibility.
[0133] The preferred range of 3σ of the brightness of the transmitted light is 1000 to 10000, 1000 to 8000, 1000 to 70000, 1300 to 10000, 1300 to 8000, 1300 to 70000, 1500 to 10000, 1500 to 8000, and 1500 to 70000.
[0134] In order to easily suppress rainbow unevenness, the surface light source preferably satisfies the following condition A. Satisfying condition A means that at least one of the half-maximum widths of the peaks of intensity in the blue wavelength region, the green wavelength region, and the red wavelength region is greater than a predetermined value (greater than 10 nm).
[0135] Fig. 9 is used to explain condition A [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )]. In addition, Fig. 9 The spectral spectrum is the spectral spectrum of the surface light source of the commonly used organic EL element.
[0136] <Condition A>
[0137] The first polarizer is placed on the surface light source, and the light L emitted from the first polarizer in the vertical direction is measured every 1nm wavelength. 1 The blue wavelength region is set to be greater than 400nm and less than 500nm, the green wavelength region is set to be greater than 500nm and less than 570nm, and the red wavelength region is set to be greater than 570nm and less than 780nm. 1 The maximum intensity of the blue wavelength region is set as B max , the L 1 The maximum intensity of the green wavelength region is set to G max , the L 1 The maximum intensity in the red wavelength region is set to R max .
[0138] will represent the B max The wavelength is set to L 1 λ B , will represent the G max The wavelength is set to L 1 λ G , will represent the R max The wavelength is set to L 1 λ R
[0139] will represent the B max The wavelength of the intensity is less than 1 / 2 of that of L 1 λ B The minimum wavelength on the negative side is set to -α B , will represent the B max The wavelength of the intensity is less than 1 / 2 of that of L 1 λ BThe minimum wavelength on the positive side is set to +α B , will represent the G max The wavelength of the intensity is less than 1 / 2 of that of L 1 λ G The maximum wavelength on the negative side is set to -α G , will represent the G max The wavelength of the intensity is less than 1 / 2 of that of L 1 λ G The minimum wavelength on the positive side is set to +α G , will represent the R max The wavelength of the intensity is less than 1 / 2 of that of L 1 λ R The maximum wavelength on the negative side is set to -α R , will represent the R max The wavelength of the intensity is less than 1 / 2 of that of L 1 λ R The maximum wavelength on the positive side is set to +α R .
[0140] [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R )] at least any one of which is greater than 10 nm.
[0141] In condition A, [+α B -(-α B )]、[+α G -(-α G )] and [+α R -(-α R It is more preferred that two or more of the above-mentioned lattices are larger than 10 nm, and it is even more preferred that all three of them are larger than 10 nm.
[0142] [+α B -(-α B )] is more preferably 15 nm or more, and even more preferably 17 nm or more. B -(-α B )] is preferably 70 nm or less, more preferably 50 nm or less, and further preferably 30 nm or less.
[0143] [+α G -(-α G )] is more preferably 15 nm or more, and even more preferably 20 nm or more. G -(-α G)] is preferably 70 nm or less, more preferably 50 nm or less, and further preferably 45 nm or less.
[0144] [+α R -(-α R )] is more preferably 15 nm or more, further preferably 20 nm or more, and further preferably 30 nm or more. R -(-α R )] is preferably below 70 nm, more preferably below 65 nm, and further preferably below 60 nm.
[0145] <Condition 2>
[0146] The in-plane phase difference (Re) was measured at a total of five locations, including four locations 10 mm from the four corners of a sample measuring 100 mm in length and 100 mm in width, and the center of the sample. Figure 5 Black circle). When the in-plane phase difference of the five parts is defined as Re1, Re2, Re3, Re4, and Re5, respectively, the average value of Re1 to Re5 is less than 2500nm. It is the average value of the in-plane phase difference calculated by the following formula (1) based on the refractive index nx in the direction of the maximum refractive index at each point, that is, the slow axis direction, the refractive index ny in the direction perpendicular to the slow axis direction, that is, the fast axis direction, and the thickness T [nm] of the biaxially stretched plastic film. In addition, in this specification, the in-plane phase difference and the phase difference in the thickness direction refer to the values at a wavelength of 550nm. In addition, when the direction of the slow axis is uneven in the plane of the biaxially stretched plastic film, the direction of the slow axis of the biaxially stretched plastic film refers to the average direction of the slow axis in the plane of the biaxially stretched plastic film.
[0147] In-plane retardation (Re) = (nx-ny) × T [nm] (1)
[0148] The direction of the slow axis and the in-plane phase difference can be measured, for example, by an instrument sold under the trade name “RETS-100” by Otsuka Electronics Co., Ltd.
[0149] When measuring the in-plane retardation (Re) or the like using an instrument with a trade name of “RETS-100” manufactured by Otsuka Electronics Co., Ltd., it is preferable to prepare for the measurement according to the following steps (A1) to (A4).
[0150] (A1) First, in order to stabilize the light source of RETS-100, leave it for more than 60 minutes after installing the light source. Then, select the rotating analyzer method and select the θ mode (the mode for angular phase difference measurement and Rth calculation). By selecting this θ mode, the worktable becomes a tilting rotation worktable.
[0151] (A2) Next, the following measurement conditions are input into RETS-100.
[0152] (Measurement conditions)
[0153] Delay measurement range: rotating analyzer method
[0154] Measuring point diameter:
[0155] Tilt angle range: 0°
[0156] ·Measurement wavelength range: above 400nm and below 800nm
[0157] Average refractive index of biaxially stretched plastic film. For example, in the case of PET film, N = 1.617. The average refractive index N of the plastic film can be calculated by the formula (N = (nx + ny + nz) / 3) based on nx, ny and nz.
[0158] Thickness: Thickness measured separately using SEM or optical microscope
[0159] (A3) Next, background data is obtained without placing a sample in the device. The device is set as a closed system, and this setting is performed every time the light source is turned on.
[0160] (A4) Then, a sample is set on a stage within the device and measurement is performed.
[0161] Condition 2 stipulates that the Re value of the biaxially stretched plastic film for optical use is 2500 nm or less.
[0162] Since the biaxially stretched plastic film is biaxially stretched, the optical biaxially stretched plastic film of the present disclosure has good mechanical strength.
[0163] In addition, since the Re of the optical biaxially stretched plastic film disclosed in the present invention is less than 2500 nm, the longitudinal and transverse stretching ratios are in an appropriate range, which can make the mechanical strength better and the tear resistance better. In addition, since the Re of the optical biaxially stretched plastic film disclosed in the present invention is less than 2500 nm, it can also contribute to the thinning of the plastic film.
[0164] Furthermore, even in the case of a biaxially stretched plastic film for optical use, sufficient mechanical strength may not be obtained if Re is too small.
[0165] In order to increase Re, the plastic film needs to be highly stretched. However, if the plastic film is highly stretched, the orientation of the polymer chains of the plastic film is consistent, which may cause problems in mechanical strength such as easy breakage in the stretching direction. Therefore, the upper limit of Re of the optical biaxially stretched plastic film disclosed in the present invention is preferably 2500 nm or less, more preferably 2000 nm or less, more preferably 1800 nm or less, more preferably 1600 nm or less, more preferably 1490 nm or less, more preferably 1400 nm or less, more preferably 1200 nm or less, more preferably 1150 nm or less, more preferably 1000 nm or less, more preferably 800 nm or less, and more preferably 600 nm or less.
[0166] Furthermore, when the thickness of the biaxially stretched plastic film for optical use is reduced to 10 μm or more and 50 μm or less, Re is preferably 1400 nm or less.
[0167] Furthermore, when the in-plane phase difference of the biaxially stretched plastic film for optical use is too small, even if biaxially stretched, sometimes the mechanical strength cannot be sufficient. Therefore, the in-plane phase difference of the biaxially stretched plastic film for optical use is preferably 20 nm or more, more preferably 100 nm or more, further preferably 300 nm or more, and further preferably 520 nm or more.
[0168] The preferred range of Re in condition 2 is 20 nm to 2500 nm, 20 nm to 2000 nm, 20 nm to 1800 nm, 20 nm to 1600 nm, 20 nm to 1490 nm, 20 nm to 1400 nm, 20 nm to 1200 nm, 20 nm to 1150 nm, 20 nm to 1000 nm, 20 nm to 800 nm, 20 nm to 600 nm, 100 nm to 2500nm, 100nm to 2000nm, 100nm to 1800nm, 100nm to 1600nm, 100nm to 1490nm, 100nm to 1400nm, 100nm to 1200nm, 100nm to 1150nm, 100nm to 1150nm, 100nm to 1000nm, 100nm to 800nm, 100nm to and 600nm or less, 300nm or more and 2500nm or less, 300nm or more and 2000nm or less, 300nm or more and 1800nm or less, 300nm or more and 1600nm or less, 300nm or more and 1490nm or less, 300nm or more and 1400nm or less, 300nm or more and 1200nm or less, 300nm or more and 1150nm or less, 300nm or more and 1000nm or less, 300nm or more and 800nm or less, 300nm or more and 600nm or less. nm or less, 520nm or more and 2500nm or less, 520nm or more and 2000nm or less, 520nm or more and 1800nm or less, 520nm or more and 1600nm or less, 520nm or more and 1490nm or less, 520nm or more and 1400nm or less, 520nm or more and 1200nm or less, 520nm or more and 1150nm or less, 520nm or more and 1000nm or less, 520nm or more and 800nm or less, 520nm or more and 600nm or less.
[0169] In the sheet-like biaxially stretched plastic film for optical use, the ratio of the measurement area satisfying both conditions 1 and 2 is preferably 50% or more, more preferably 70% or more, further preferably 90% or more, and further preferably 100%.
[0170] In addition, in the case where a plurality of samples involved in the measurement of conditions 1 and 2 can be collected from a roll of optical biaxially stretched plastic film, it is preferred that the samples collected from a specified position in the width direction of the roll satisfy the conditions in most of the conveying direction of the roll. By satisfying the aforementioned structure, if a biaxially stretched plastic film for optical use at a specified position in the width direction of the roll is picked up, a biaxially stretched plastic film for optical use that can exert the effects of the present disclosure can be produced. That is, the biaxially stretched plastic film for optical use in a roll does not need to satisfy conditions 1 and 2 in the entire width direction, as long as conditions 1 and 2 are satisfied at least in the specified position in the width direction. In addition, for a rolled plastic film, various physical properties are prone to change in the width direction, but various physical properties are almost the same in the conveying direction. Therefore, in the case where the samples collected from a specified position in the width direction of the roll satisfy conditions 1 and 2, for the parts with the same position in the width direction, it can be simulated that conditions 1 and 2 are satisfied in the entire conveying direction of the roll.
[0171] Furthermore, in the biaxially stretched plastic film for optical use, it is preferred that at least any of the following conditions 3 and 4 be satisfied.
[0172] <Condition 3>
[0173] The difference between the maximum value of Re1, Re2, Re3, Re4, and Re5 obtained under Condition 2 and the minimum value of Re1 to Re5 is preferably 5 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more.
[0174] By increasing the difference, condition 4 can be easily satisfied.
[0175] In order to suppress variations in optical characteristics and mechanical strength, the difference is preferably 100 nm or less, more preferably 70 nm or less.
[0176] <Condition 4>
[0177] The directions of the slow axes of the five locations of condition 2 are measured. When the angles formed by any one side of the measurement area of condition 2 and the direction of the slow axis of each measurement location are defined as D1 (angle of the measurement point of Re1), D2, D3, D4, and D5, respectively, it is preferred that the difference between the maximum value and the minimum value of D1 to D5 is 5.0 degrees or more. In addition, "any one side of the measurement area of condition 2" refers to any one side of the measurement sample (100 mm × 100 mm) of condition 2. Any one side can be any side of the longitudinal and lateral sides of the sample as long as all of D1 to D5 are based on the same side.
[0178] Condition 4 stipulates that the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is 5.0 degrees or more. If the difference is 5.0 degrees or more, when observing with polarized sunglasses or polarized goggles, no black screen can be observed in the sample area, or the black screen can be reduced.
[0179] Conventional optical plastic films are designed in such a way that the direction of the slow axis is not offset in a narrow area, but the optical biaxially stretched plastic film satisfying condition 4 intentionally offsets the direction of the slow axis in a narrow area, and in this respect, the structure is different from conventional optical films. The narrow area refers to the size of the measurement sample (100 mm × 100 mm). In addition, it is also possible to use an optical biaxially stretched plastic film in which the tensile strength is weakened and the direction of the slow axis is not fully consistent. By satisfying condition 4, it is easier to satisfy conditions 1 and 2. In addition, by satisfying condition 4, it is easy to make the bending resistance described later good.
[0180] The difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is preferably 6.0 degrees or more, more preferably 8.0 degrees or more, and further preferably 10.0 degrees or more.
[0181] Furthermore, when the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is too large, the orientation of the optical biaxially stretched plastic film tends to be reduced and the mechanical strength tends to be reduced. Therefore, the difference is preferably 20.0 degrees or less, more preferably 17.0 degrees or less, and further preferably 15.0 degrees or less.
[0182] In condition 4, the preferred range of the difference between the maximum value and the minimum value of D1 to D5 can be, for example, greater than 5.0 degrees and less than 20.0 degrees, greater than 6.0 degrees and less than 20.0 degrees, greater than 8.0 degrees and less than 20.0 degrees, greater than 10.0 degrees and less than 20.0 degrees, greater than 5.0 degrees and less than 17.0 degrees, greater than 6.0 degrees and less than 17.0 degrees, greater than 8.0 degrees and less than 17.0 degrees, greater than 10.0 degrees and less than 17.0 degrees, greater than 5.0 degrees and less than 15.0 degrees, greater than 6.0 degrees and less than 15.0 degrees, greater than 8.0 degrees and less than 15.0 degrees, and greater than 10.0 degrees and less than 15.0 degrees.
[0183] D1 to D5 of the biaxially stretched plastic film for optical use according to one embodiment of the present disclosure are preferably 5 degrees to 30 degrees or 60 degrees to 85 degrees, more preferably 7 degrees to 25 degrees or 65 degrees to 83 degrees, and further preferably 10 degrees to 23 degrees or 67 degrees to 80 degrees.
[0184] By making D1 to D5 respectively 5 degrees or more or 85 degrees or less, it is easy to suppress a black screen when viewing with polarized sunglasses or polarized goggles, etc. In addition, by making D1 to D5 respectively 30 degrees or less or 60 degrees or more, it is easy to suppress a decrease in mechanical strength due to a decrease in the orientation of the optical biaxially stretched plastic film.
[0185] Regarding the optical biaxially stretched plastic film of one embodiment of the present disclosure, the in-plane phase difference relative to the phase difference in the thickness direction (in-plane phase difference / phase difference in the thickness direction) is preferably 0.10 or less. In this specification, "Re / Rth" is sometimes used to represent the in-plane phase difference relative to the phase difference in the thickness direction. Re / Rth can be measured, for example, as follows.
[0186] The in-plane phase differences measured at 5 locations of the above sample are defined as Re1, Re2, Re3, Re4 and Re5, respectively, and the phase differences in the thickness direction measured at 5 locations of the above sample are defined as Rth1, Rth2, Rth3, Rth4 and Rth5, respectively.
[0187] The biaxially stretched plastic film for optical use preferably has an average value of Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 of 0.10 or less.
[0188] A smaller ratio of the in-plane phase difference to the phase difference in the thickness direction (Re / Rth) means that the biaxial stretching of the biaxially stretched plastic film is close to equal biaxiality. Therefore, by making Re / Rth 0.10 or less, the mechanical strength of the biaxially stretched plastic film can be improved. Re / Rth is more preferably 0.07 or less, and further preferably 0.05 or less. The lower limit of Re / Rth is about 0.01.
[0189] The Re / Rth of a completely uniaxially stretched plastic film is 2.0. A commonly used uniaxially stretched plastic film is also slightly stretched in the conveying direction. Therefore, the Re / Rth of a commonly used uniaxially stretched plastic film is about 1.0.
[0190] Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 are each preferably 0.10 or less, more preferably 0.07 or less, and still more preferably 0.05 or less. The lower limit of these ratios is about 0.01.
[0191] The phase difference (Rth) in the thickness direction is expressed by the following formula based on the refractive index nx in the direction of the maximum refractive index, i.e., the slow axis direction, the refractive index ny in the direction perpendicular to the slow axis direction, i.e., the fast axis direction, the refractive index nz in the thickness direction of the plastic film, and the thickness T [nm] of the plastic film.
[0192] Rth=((nx+ny) / 2-nz)×T[nm]
[0193] The retardation (Rth) in the thickness direction of the biaxially stretched plastic film for optics is preferably 2000 nm or more, more preferably 3000 nm or more, and further preferably 4000 nm or more. The upper limit of Rth is about 10000 nm, preferably 8000 nm or less, and more preferably 7000 nm or less. By setting Rth to the above range, rainbow unevenness can be more easily suppressed.
[0194] Preferred ranges of Rth of biaxially stretched plastic films for optical purposes include 2000 nm to 10000 nm, 2000 nm to 8000 nm, 2000 nm to 7000 nm, 3000 nm to 10000 nm, 3000 nm to 8000 nm, 3000 nm to 7000 nm, 4000 nm to 10000 nm, 4000 nm to 8000 nm, and 4000 nm to 7000 nm.
[0195] In order to make the Rth of the optical biaxially stretched plastic film within the above range, it is preferred to increase the longitudinal and transverse stretching ratios. By increasing the longitudinal and transverse stretching ratios, the refractive index nz in the thickness direction of the biaxially stretched plastic film becomes smaller, so Rth can be easily increased.
[0196] <Details of folding test>
[0197] Furthermore, satisfying conditions 1 and 2 is preferable in that the mechanical strength of the biaxially stretched plastic film for optical use can be improved, for example, the breakability in the stretching direction can be improved, and the bending resistance can be improved.
[0198] On the other hand, for plastic films that do not satisfy conditions 1 and 2, the film breaks after the bending test, or a strong bending tendency remains. Specifically, a uniaxially stretched film such as Patent Document 1 breaks when the bending test is performed along the slow axis, and a strong bending tendency remains when the bending test is performed in a direction perpendicular to the slow axis. In addition, a commonly used biaxially stretched film has a strong bending tendency remaining when the bending test is performed in a direction perpendicular to the slow axis.
[0199] On the other hand, the biaxially stretched plastic film for optical use disclosed in the present invention is preferred in that it can suppress the occurrence of bending tendency remaining or breakage after the bending test regardless of the bending direction. In order to easily improve the bending resistance, it is preferred that the plastic film satisfies condition 4.
[0200] like Figure 6As shown in (A), in the continuous folding test, first, the side 10C and the side 10D opposite to the side 10C of the optical biaxially stretched plastic film 10 are fixed by the parallelly arranged fixing parts 60. The fixing parts 60 can slide in the horizontal direction.
[0201] Then, if Figure 6 As shown in (B), by moving the fixing parts 60 in a manner close to each other, the optical biaxially stretched plastic film 10 is deformed in a folded manner, and then, as shown in FIG. Figure 6 As shown in (C), the fixing part 60 is moved to a position where the interval between two opposing sides of the optical biaxially stretched plastic film 10 fixed by the fixing part 60 becomes 10 mm, and then the fixing part 60 is moved in the opposite direction to eliminate the deformation of the optical biaxially stretched plastic film 10.
[0202] Through Figure 6 By moving the fixing part 60 as shown in (A) to (C), the optical biaxially stretched plastic film 10 can be folded 180 degrees. In addition, the continuous folding test is performed in a manner that the curved part 10E of the optical biaxially stretched plastic film 10 does not protrude from the lower end of the fixing part 60, and by controlling the interval when the fixing parts 60 are closest to each other to be 10 mm, the interval between the two opposing sides of the optical film 10 can be 10 mm.
[0203] Preferably, the optical biaxially stretched plastic film does not produce cracks or breaks after the folding test shown in the embodiment is performed 100,000 times (more preferably after 300,000 times). In addition, with respect to the optical biaxially stretched plastic film, after the folding test shown in the embodiment is performed 100,000 times (more preferably after 300,000 times), when the measurement sample is placed on a horizontal table, the angle at which the end of the sample is lifted from the table is preferably less than 20 degrees, more preferably less than 15 degrees. The angle of the sample being lifted from the end is less than 15 degrees, which means that it is difficult to produce a tendency caused by folding. In addition, for any of the average directions of the slow axis direction and the average direction of the fast axis direction of the optical biaxially stretched plastic film, it is preferred that the aforementioned results are shown (no cracks, breaks, and tendencies caused by folding are produced. The angle of lift at the end of the sample after the test is less than 20 degrees).
[0204] Furthermore, a uniaxially stretched plastic film will break in the stretching direction when subjected to a folding test, and will have a strong tendency to remain bent in a direction perpendicular to the stretching direction.
[0205] <Biaxially stretched plastic film for optical use>
[0206] The laminated structure of the biaxially stretched plastic film for optical use may be a single-layer structure or a multi-layer structure, of which a single-layer structure is preferred.
[0207] For biaxially stretched plastic films for optical use, in order to improve mechanical strength while suppressing black screen and rainbow unevenness when viewed with polarized sunglasses or polarized goggles, it is necessary to make the "brightness difference deviation 3σ" greater than 100 and Re less than 2500nm. In addition, in order to reduce the in-plane phase difference of the biaxially stretched plastic film for optical use, it is important to make the longitudinal and transverse stretching close to equal. Regarding fine stretching control, in a multilayer structure, it is difficult to perform fine stretching control due to the difference in physical properties of each layer, but a single-layer structure is preferred in that it is easy to perform fine stretching control.
[0208] As the resin component constituting the biaxially stretched plastic film for optics, polyester, polyamide, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyetherketone, polymethyl methacrylate, polycarbonate, polyurethane and amorphous olefin (Cyclo-Olefin-Polymer: COP) etc. can be cited. Among them, polyester is preferred from the aspect of easy improvement of mechanical strength. That is, the biaxially stretched plastic film for optics is preferably a polyester film.
[0209] Examples of the polyester constituting the polyester film include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT). Among them, PET is preferred because it is easy to make the "brightness difference deviation 3σ" 100 or more.
[0210] The biaxially stretched plastic film for optical use may contain additives such as ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, antigelling agents and surfactants.
[0211] The lower limit of the thickness of the optical biaxially stretched plastic film is preferably 10 μm or more, more preferably 15 μm or more, more preferably 20 μm or more, more preferably 25 μm or more, more preferably 30 μm or more, and the upper limit is preferably 200 μm or less, more preferably 180 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, more preferably 50 μm or less. In order to achieve thin film, the thickness of the optical biaxially stretched plastic film is preferably 50 μm or less.
[0212] By setting the thickness to 10 μm or more, the mechanical strength can be easily improved. In addition, by setting the thickness to 200 μm or less, the condition 2 can be easily satisfied.
[0213] The preferred range of the thickness of the biaxially stretched plastic film is, for example, 10 μm to 200 μm, 15 μm to 200 μm, 20 μm to 200 μm, 25 μm to 200 μm, 30 μm to 200 μm, 10 μm to 180 μm, 15 μm to 180 μm, 20 μm to 180 μm, 25 μm to 180 μm, 30 μm to 180 μm, 10 μm to 150 μm, 15 μm to 150 μm, 20 μm to 150 μm, 25 μm to 150 μm, 30 μm to 150 μm, 10 μm to 100 μm, 15 μm to 150 μm, and less than 100μm, 20μm or more and less than 100μm, 25μm or more and less than 100μm, 30μm or more and less than 100μm, 10μm or more and less than 80μm, 15μm or more and less than 80μm, 20μm or more and less than 80μm, 25μm or more and less than 80μm, 30μm or more and less than 80μm, 10μm or more and less than 60μm, 15μm or more and less than 60μm, 20μm or more and less than 60μm, 25μm or more and less than 60μm, 30μm or more and less than 60μm, 10μm or more and less than 50μm, 15μm or more and less than 50μm, 20μm or more and less than 50μm, 25μm or more and less than 50μm, 30μm or more and less than 50μm.
[0214] Regarding the biaxially stretched plastic film for optical use, the haze according to JIS K7136:2000 is preferably 3.0% or less, more preferably 2.0% or less, further preferably 1.5% or less, and further preferably 1.0% or less.
[0215] In addition, regarding the biaxially stretched plastic film for optical use, the total light transmittance of JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.
[0216] In order to improve the mechanical strength, the biaxially stretched plastic film for optical use is more preferably a biaxially stretched polyester film. Furthermore, the biaxially stretched plastic film for optical use is more preferably a single-layer structure of a polyester resin layer.
[0217] The optical biaxially stretched plastic film can be obtained by stretching a resin layer containing components constituting the plastic film. The stretching method includes biaxial stretching such as sequential biaxial stretching and simultaneous biaxial stretching. Among the optical biaxially stretched plastic films, biaxially stretched polyester films are preferred, and biaxially stretched polyethylene terephthalate films are more preferred.
[0218] -Sequential biaxial stretching-
[0219] In the sequential biaxial stretching, after the cast film is stretched in the conveying direction, stretching in the width direction of the film is performed.
[0220] The stretching in the conveying direction is usually implemented by the difference in the peripheral speed of a pair of stretching rollers. The stretching in the conveying direction can be carried out in one stage, or it can be carried out in multiple stages using multiple stretching rollers. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferred to bring multiple clamping rollers close to the stretching rollers. The stretching ratio in the conveying direction is usually more than 2 times and less than 15 times. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferably more than 2 times and less than 7 times, more preferably more than 3 times and less than 5 times, and further preferably more than 3 times and less than 4 times.
[0221] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature is preferably higher than the glass transition temperature of the resin and lower than the glass transition temperature + 100° C. In the case of PET, it is preferably higher than 70° C. and lower than 120° C., more preferably higher than 80° C. and lower than 110° C., and further preferably higher than 95° C. and lower than 110° C.
[0222] Regarding the stretching temperature, by rapidly heating the film, the stretching interval at low temperature is shortened, thereby there is a tendency for the average value of the in-plane phase difference to become smaller. On the other hand, by slowly heating the film, the stretching interval at low temperature is extended, thereby there is a tendency for the orientation to be improved, the average value of the in-plane phase difference to be increased, and the deviation of the slow axis to be reduced.
[0223] Furthermore, when heating during stretching, it is preferred to use a heater that generates turbulence. By utilizing wind containing turbulence for heating, a temperature difference is generated in a fine region within the film surface, and a fine offset is generated on the orientation axis due to the temperature difference, so that conditions 1 and 4 can be easily satisfied.
[0224] In-line coating can also be used to impart lubricity, adhesion, antistatic properties, and other functions to the film stretched along the conveying direction. In addition, before in-line coating, surface treatments such as corona treatment, flame treatment, and plasma treatment can be performed as needed.
[0225] The coating film formed in the in-line coating is an extremely thin coating film having a thickness of about 10 nm or more and about 2000 nm or less (in addition, the coating film is stretched to be thinner by stretching treatment). In this specification, such a thin layer is not counted as the number of layers constituting the biaxially stretched plastic film for optical use.
[0226] The stretching in the width direction is usually carried out by conveying the film in the width direction while holding the two ends of the film with a clamp using a tenter method. The stretching ratio in the width direction is usually more than 2 times and less than 15 times. In order to suppress excessive deviations of optical properties such as in-plane phase difference, it is preferably more than 2 times and less than 5 times, more preferably more than 3 times and less than 5 times, and further preferably more than 3 times and less than 4.5 times. In addition, it is preferred that the width stretching ratio is higher than the longitudinal stretching ratio.
[0227] The stretching temperature is preferably above the glass transition temperature of the resin and below the glass transition temperature + 120°C, and the temperature is preferably increased from the upstream to the downstream. Specifically, when the transverse stretching interval is divided into two equal parts, the difference between the upstream temperature and the downstream temperature is preferably 20°C or more, more preferably 30°C or more, further preferably 35°C or more, and further preferably 40°C or more. In addition, in the case of PET, the stretching temperature in the first stage is preferably 80°C or more and 120°C or less, more preferably 90°C or more and 110°C or less, and further preferably 95°C or more and 105°C or less.
[0228] In order to impart planarity and dimensional stability, the plastic film after being sequentially biaxially stretched as described above is preferably subjected to heat treatment in a tenter at a temperature above the stretching temperature and below the melting point. Specifically, in the case of PET, heat fixation is preferably performed in the range of 150°C to 255°C, more preferably 200°C to 250°C. In addition, in order to suppress excessive deviations in optical properties such as in-plane phase difference, additional stretching of 1% to 10% is preferably performed in the first half of the heat treatment.
[0229] After the plastic film is heat-treated, it is slowly cooled to room temperature and then rolled up. In addition, as needed, relaxation treatment can also be used during heat treatment and slow cooling. In order to suppress excessive deviations of optical properties such as in-plane phase difference, the relaxation rate during heat treatment is preferably 0.5% or more and 5% or less, more preferably 0.5% or more and 3% or less, more preferably 0.8% or more and 2.5% or less, and more preferably 1% or more and 2% or less. In addition, in order to suppress excessive deviations of optical properties such as in-plane phase difference, the relaxation rate during slow cooling is preferably 0.5% or more and 3% or less, more preferably 0.5% or more and 2% or less, more preferably 0.5% or more and 1.5% or less, and more preferably 0.5% or more and 1.0% or less. In order to make the planarity good, the temperature during slow cooling is preferably 80°C or more and 150°C or less, more preferably 90°C or more and 130°C or less, more preferably 100°C or more and 130°C or less, and more preferably 100°C or more and 120°C or less.
[0230] - Simultaneous biaxial stretching -
[0231] Simultaneous biaxial stretching is to introduce the cast film into a simultaneous biaxial tenter, hold both ends of the film with a clamp while conveying, and stretch it simultaneously and / or stepwise in the conveying direction and the width direction. As a simultaneous biaxial stretching machine, there are a pantograph type, a screw type, a drive motor type, and a linear motor type, but the drive motor type or the linear motor type that can arbitrarily change the stretch ratio and can perform relaxation treatment at any place is preferred.
[0232] The ratio of the simultaneous biaxial stretching is usually 6 times or more and 50 times or less in terms of area ratio. In order to suppress excessive deviations of optical properties such as in-plane phase difference, the area ratio is preferably 8 times or more and 30 times or less, more preferably 9 times or more and 25 times or less, further preferably 9 times or more and 20 times or less, and further preferably 10 times or more and 15 times or less. In the simultaneous biaxial stretching, it is preferred that the stretching ratio in the transmission direction and the stretching ratio in the width direction are within the range of 2 times or more and 15 times or less, and are adjusted in a manner to become the aforementioned area ratio.
[0233] In the case of simultaneous biaxial stretching, in order to suppress the orientation difference in the plane, it is preferable that the stretching ratio in the conveying direction and the width direction are substantially the same, and the stretching speed in the conveying direction and the width direction are also substantially the same.
[0234] In order to suppress excessive deviation of optical properties such as in-plane phase difference, the stretching temperature of the simultaneous biaxial stretching is preferably not less than the glass transition temperature of the resin and not more than the glass transition temperature + 120° C. In the case of PET, it is preferably not less than 80° C. and not more than 160° C., more preferably not less than 90° C. and not more than 150° C., and further preferably not less than 100° C. and not more than 140° C.
[0235] In order to impart flatness and dimensional stability, the film subjected to simultaneous biaxial stretching is preferably subjected to heat treatment in a heat fixing chamber in a tenter at a temperature above the stretching temperature and below the melting point. The conditions for the heat treatment are the same as those for the heat treatment after the sequential biaxial stretching.
[0236] <Shape, size>
[0237] The optical biaxially stretched plastic film may be in the form of a single sheet cut into a specified size, or in the form of a roll in which a long strip is wound into a roll. In addition, the size of the single sheet is not particularly limited, but the maximum diameter is about 2 inches or more and 500 inches or less, and in the present disclosure, it is preferably 30 inches or more and 80 inches or less. "Maximum diameter" refers to the maximum length when connecting any two points of the optical film. For example, when the optical film is rectangular, the diagonal of the rectangular area is the maximum diameter. In addition, when the optical film is circular, the diameter is the maximum diameter.
[0238] The width and length of the roll are not particularly limited. Generally speaking, the width is about 500 mm or more and 3000 mm or less, and the length is about 100 m or more and 5000 m or less. The roll-shaped optical film can be cut into a single piece for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll with unstable physical properties.
[0239] In addition, the shape of a single sheet is not particularly limited, and can be, for example, a polygon (triangle, quadrilateral, pentagon, etc.), a circle, or a random amorphous shape. More specifically, when the optical film is a quadrilateral, the aspect ratio is not particularly limited as long as it does not cause problems as a display screen. For example, aspect ratios of 1:1, 4:3, 16:10, 16:9, 2:1, etc. can be cited.
[0240] [Functional membrane]
[0241] In the biaxially stretched plastic film for optical use disclosed in the present invention, functional layers such as a hard coating layer, a low refractive index layer, a high refractive index layer, an anti-glare layer, an antifouling layer, an antistatic layer, a barrier layer, an antifog layer and a transparent conductive layer can be further formed to make a functional film.
[0242] That is, the functional film of the present disclosure is a film having a functional layer on the above-mentioned biaxially stretched plastic film for optical use of the present disclosure. The biaxially stretched plastic film for optical use may have a functional layer on at least one side or on both sides.
[0243] In order to maintain mechanical properties and suppress excessive deviation of optical properties such as in-plane phase difference to effectively suppress black screen, the overall thickness of the functional film is preferably 100 μm or less, more preferably 60 μm or less. In addition, in the functional film, the balance between the thickness of the biaxially stretched plastic film and the thickness of the functional layer is preferably 10:4 to 10:0.5.
[0244] Regarding the functional film, it is sufficient that the optical biaxially stretched plastic film as the substrate satisfies conditions 1 and 2, and more preferably satisfies the following condition 1A. The preferred embodiment of condition 1A is the same as the preferred embodiment of the above-mentioned condition 1. In addition, regarding measurement 1A and measurement 2A, except that the biaxially stretched plastic film is changed to a functional film, it is the same as the above-mentioned measurement 1 and measurement 2 of the optical biaxially stretched plastic film of the present disclosure.
[0245] <Condition 1A>
[0246] The luminance difference (L1.n-L2.n) between the luminance obtained in the following measurement 1A and the luminance obtained in the following measurement 2A is calculated at 100 measurement points, and the "luminance difference deviation 3σ" calculated from the luminance difference at the 100 measurement points is 100 or more.
[0247] Measurement 1A
[0248] A 1A measurement sample is prepared in which a 1st polarizer, a functional film, and a 2nd polarizer are arranged in this order on a surface light source. In the 1A measurement sample, the direction of the slow axis of the optical biaxially stretched plastic film constituting the functional film is arranged to be approximately perpendicular to the direction of the absorption axis of the 1st polarizer, and the absorption axis of the 2nd polarizer is arranged to be approximately perpendicular to the direction of the absorption axis of the 1st polarizer.
[0249] Make the surface light source of the 1A measurement sample display white, measure the brightness of the transmitted light emitted from the second polarizer side at measurement points of 100×100 set at equal intervals in any first area, extract any 100 points in a horizontal column from the measurement results, and use them as the 1st to 100th measurement points, respectively, define the brightness of the 1st measurement point as L1.1, the brightness of the 100th measurement point as L1.100, and the brightness of the nth measurement point as L1.n.
[0250] Measurement 2A
[0251] A 2A measurement sample is prepared by arranging the first polarizer and the second polarizer in this order on the same surface light source as the measurement 1A. In the 2A measurement sample, the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer.
[0252] Make the surface light source of the 2A measurement sample display white, measure the brightness of the transmitted light emitted from the second polarizer side at 100×100 measurement points set at equal intervals in an area roughly consistent with the first measurement area, extract any 100 points in a horizontal column from the measurement results, and use them as the 1st to 100th measurement points, respectively, define the brightness of the 1st measurement point as L2.1, the brightness of the 100th measurement point as L2.100, and the brightness of the nth measurement point as L2.n.
[0253] <Functional Layer>
[0254] As the functional layer, a hard coat layer, a low refractive index layer, a high refractive index layer, an anti-glare layer, an antifouling layer, an antistatic layer, a barrier layer, an anti-fog layer and a transparent conductive layer can be cited. The functional layer can be one selected from the above-mentioned layers, or two or more layers can be stacked. These functional layers are preferably optically isotropic functional layers. Optical isotropy means that the in-plane phase difference is less than 20nm, preferably less than 10nm, and more preferably less than 5nm.
[0255] In addition, the functional layer can also be a layer composed of two or more of the above functions. That is, in this specification, the description of each functional layer such as hard coating, low refractive index layer, high refractive index layer, anti-glare layer, antifouling layer, antistatic layer, barrier layer, anti-fog layer and transparent conductive layer refers not only to functional layers with individual functions, but also to functional layers with composite functions. For example, the hard coating includes antifouling hard coating, anti-glare hard coating and high refractive index hard coating. In addition, the antifouling layer includes anti-glare antifouling layer and low refractive index antifouling layer.
[0256] Specific examples of functional layers include the following (1) to (9). In addition, in the following (1) to (9), the left side represents the layer located on the side of the biaxially stretched plastic film for optical use. In addition, in the following (1) to (9), the antifouling layer, hard coating layer, high refractive index layer, low refractive index layer and antiglare layer may also be composite functional layers having other functions. For example, the low refractive index layer of (1), (2), (7) to (9) preferably has an antifouling layer. In addition, the antiglare layer of (3) and the antifouling layer of (5) preferably have hard coating properties.
[0257] (1) A structure having a low refractive index layer on a hard coat layer.
[0258] (2) A structure having a high refractive index layer and a low refractive index layer on a hard coat layer.
[0259] (3) Single-layer structure of the anti-glare layer.
[0260] (4) A structure having an antiglare layer on a hard coat layer.
[0261] (5) Single-layer structure of the antifouling layer.
[0262] (6) A structure having an antifouling layer on a hard coat layer.
[0263] (7) A structure having a low refractive index layer on the anti-glare layer.
[0264] (8) A structure having a low refractive index layer on a high refractive index hard coat layer.
[0265] (9) A structure having an antiglare layer and a low refractive index layer on a hard coat layer.
[0266] Hereinafter, the hard coat layer, the low refractive index layer, the high refractive index layer, the antiglare layer, and the antifouling layer, which are representative examples of the functional layer, will be specifically described.
[0267] <Hard Coating>
[0268] In order to improve the scratch resistance, the hard coat layer as an example of the functional layer preferably contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.
[0269] Thermosetting resin composition is a composition containing at least a thermosetting resin and is a resin composition that is cured by heating. Examples of thermosetting resins include acrylic resins, polyurethane resins, phenolic resins, urea melamine resins, epoxy resins, unsaturated polyester resins, silicone resins, and the like. For thermosetting resin compositions, a curing agent is added to these curable resins as required.
[0270] Ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). As the ionizing radiation curable functional group, ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, allyl, and epoxy, oxetane, etc. can be listed. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and a compound having more than two ethylenically unsaturated bond groups is more preferred, wherein, a (meth) acrylate compound having more than two ethylenically unsaturated bond groups is further preferred. As a (meth) acrylate compound having more than two ethylenically unsaturated bond groups, any one of a monomer and an oligomer can be used.
[0271] Furthermore, ionizing radiation refers to radiation in electromagnetic waves or charged particle beams that has an energy quantum capable of polymerizing or cross-linking molecules, and is usually ultraviolet (UV) or electron beam (EB). In addition, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays may also be used.
[0272] In the present specification, (meth)acrylate means acrylate or methacrylate, (meth)acrylic acid means acrylic acid or methacrylic acid, and (meth)acryloyl means acryloyl or methacryloyl.
[0273] In order to achieve good scratch resistance, the thickness of the hard coating layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, in order to suppress curling, the thickness of the hard coating layer is preferably 100 μm or less, more preferably 50 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less. In order to achieve good bending resistance, the thickness of the hard coating layer is preferably 10 μm or less, and more preferably 8 μm or less.
[0274] <Low Refractive Index Layer>
[0275] The low refractive index layer has the function of improving the anti-reflective property of the optical film and facilitating the suppression of rainbow unevenness when observed with the naked eye. Here, rainbow unevenness refers to a rainbow-like interference pattern observed when linearly polarized light passing through a polarizer passes through a birefringent body such as a stretched plastic film due to the disorder of the polarization state of the linearly polarized light.
[0276] Light from the inside of the image display device toward the observer side is linearly polarized when passing through the polarizer, but after passing through the optical biaxially stretched plastic film, the polarization state of the linearly polarized light is disturbed and becomes a mixture of P waves and S waves. In addition, since there is a difference between the reflectivity of the P wave and the reflectivity of the S wave, and the reflectivity difference is wavelength-dependent, it is conceivable that rainbow unevenness can be seen with the naked eye. Here, it is conceivable that in the case of having a low refractive index layer on the optical biaxially stretched plastic film, the aforementioned reflectivity difference can be reduced, so the rainbow unevenness can be easily suppressed.
[0277] The low refractive index layer is preferably formed on the side farthest from the optical biaxially stretched plastic film. Furthermore, by forming a high refractive index layer described later adjacent to the low refractive index layer on the optical biaxially stretched plastic film side relative to the low refractive index layer, the antireflection property can be further improved and rainbow unevenness can be more easily suppressed.
[0278] The refractive index of the low refractive index layer is preferably 1.10 to 1.48, more preferably 1.20 to 1.45, more preferably 1.26 to 1.40, more preferably 1.28 to 1.38, and more preferably 1.30 to 1.32.
[0279] In addition, the thickness of the low-refractive index layer is preferably 80 nm or more and 120 nm or less, more preferably 85 nm or more and 110 nm or less, more preferably 90 nm or more and 105 nm or less. In addition, the thickness of the low-refractive index layer is preferably greater than the average particle diameter of low-refractive index particles such as hollow particles.
[0280] As a method for forming a low refractive index layer, it can be roughly divided into a wet method and a dry method. As a wet method, a method of forming by a sol-gel method using a metal alkoxide or the like, a method of forming by coating a low refractive index resin such as a fluororesin, and a method of forming by coating a low refractive index layer containing low refractive index particles in a resin composition. As a dry method, the following method can be cited: selecting particles with a desired refractive index from the low refractive index particles described later, and forming by a physical vapor deposition method or a chemical vapor deposition method.
[0281] The wet method is superior to the dry method in terms of production efficiency, suppression of oblique reflection hue, and chemical resistance. In addition, in the wet method, for the purpose of adhesion, water resistance, scratch resistance, and low refractive index, it is preferably formed by using a coating liquid for forming a low refractive index layer containing low refractive index particles in a binder resin composition.
[0282] The low refractive index layer is often located on the outermost surface of the optical film. Therefore, the low refractive index layer is required to have good scratch resistance, and the commonly used low refractive index layer is also designed to have a predetermined scratch resistance.
[0283] In recent years, in order to reduce the refractive index of the low refractive index layer, hollow particles with large particle size are used as low refractive index particles. The inventors have found the following problem (hereinafter, this problem is sometimes referred to as "oil dust resistance"): Even when no damage is observed when the surface of the low refractive index layer containing hollow particles with large particle size is rubbed with an object only attached with fine solid matter (such as sand) or an object only attached with oil, damage will occur when rubbing with an object attached with both solid matter and oil. The action of wiping with an object attached with solid matter and oil is equivalent to the action of a user operating a touch panel type image display device with a finger attached with oil contained in cosmetics and food, etc. and sand contained in the atmosphere.
[0284] It is preferable to improve the oil dust resistance of the low refractive index layer in order to maintain the rainbow unevenness suppression effect for a long period of time.
[0285] The inventors have studied and found that the above-mentioned damage is mainly caused by a part of the hollow particles contained in the low refractive index layer being defective or the hollow particles falling off. As the reason, it is considered that the concavoconvex caused by the hollow particles formed on the surface of the low refractive index layer is larger. That is, when wiping the surface of the low refractive index layer with a finger attached with solids and oil, the oil becomes an adhesive, and under the state that the solid is attached to the finger, the finger moves on the surface of the low refractive index layer. At this time, it can be imagined that: the phenomenon that a part of the solid (such as the sharp part of sand) easily produces enters the concave portion of the low refractive index layer surface and the solid that enters the concave portion passes through the concave portion and crosses the convex portion (hollow particles) together with the finger, and now a larger force can be applied to the convex portion (hollow particles), so the hollow particles can be damaged or fall off. In addition, it can be imagined that the resin itself located in the concave portion is also damaged due to the friction of the solid, and the hollow particles are more likely to fall off due to the damage of the resin.
[0286] In order to improve the oil dust resistance, the low refractive index particles preferably include hollow particles and non-hollow particles.
[0287] In order to improve the oil dust resistance, it is preferred to use hollow particles and non-hollow particles together as the low refractive index particles and to uniformly disperse the hollow particles and the non-hollow particles.
[0288] The material of the hollow particles and the non-hollow particles can be any of inorganic compounds such as silica and magnesium fluoride, and organic compounds, but silica is preferred for lowering the refractive index and increasing strength. The following description will focus on hollow silica particles and non-hollow silica particles.
[0289] Hollow silica particles refer to particles that have an outer shell layer composed of silica, and the inside of the particles surrounded by the outer shell layer is hollow, and air is contained in the hollow. Hollow silica particles are particles whose refractive index is reduced in proportion to the occupancy rate of gas compared with the original refractive index of silica by containing air. Non-hollow silica particles refer to particles that are not hollow inside like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles.
[0290] The shapes of the hollow silica particles and non-hollow silica particles are not particularly limited, and may be substantially spherical shapes such as true spheres, rotational ellipsoids, and polyhedrons that can approximate spheres. Of these, true spheres, rotational ellipsoids, or substantially spherical shapes are preferred in consideration of scratch resistance.
[0291] Hollow silica particles contain air inside, so they play a role in reducing the refractive index of the entire low refractive index layer. By using hollow silica particles with a large particle size that has improved the air ratio, the refractive index of the low refractive index layer can be further reduced. On the other hand, hollow silica particles have a tendency to deteriorate in mechanical strength. Especially in the case of hollow silica particles with a large particle size that has improved the air ratio, there is a tendency to easily reduce the scratch resistance of the low refractive index layer.
[0292] The non-hollow silica particles play a role in improving the scratch resistance of the low refractive index layer by being dispersed in the binder resin.
[0293] In order to make the binder resin contain hollow silica particles and non-hollow silica particles at a high concentration and make the particles uniformly dispersed in the resin along the film thickness direction, it is preferred to set the average particle size of the hollow silica particles and the average particle size of the non-hollow silica particles in a manner close to and entering the hollow silica particles. Specifically, the ratio of the average particle size of the non-hollow silica particles to the average particle size of the hollow silica particles (average particle size of the non-hollow silica particles / average particle size of the hollow silica particles) is preferably less than 0.29, more preferably less than 0.20. In addition, the ratio of the average particle size is preferably more than 0.05.
[0294] Considering the optical properties and mechanical strength, the average particle size of the hollow silica particles is preferably 20 nm or more and 100 nm or less. In order to easily reduce the refractive index of the entire low refractive index layer, the average particle size of the hollow silica particles is more preferably 50 nm or more and 100 nm or less, and further preferably 60 nm or more and 80 nm or less.
[0295] In addition, in consideration of dispersibility while preventing aggregation of the non-hollow silica particles, the average particle size of the non-hollow silica particles is preferably 5 nm to 20 nm, and more preferably 10 nm to 15 nm.
[0296] It is preferred that the hollow silica particles and non-hollow silica particles have their surfaces coated with a silane coupling agent, and it is more preferred to use a silane coupling agent having a (meth)acryloyl group or an epoxy group.
[0297] By subjecting the silica particles to a surface treatment using a silane coupling agent, the affinity between the silica particles and the binder resin is improved, and aggregation of the silica particles is less likely to occur. Therefore, the silica particles are easily dispersed uniformly.
[0298] Examples of the silane coupling agent include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-Triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isopropyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane. It is particularly preferable to use one or more selected from 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane.
[0299] The more the content of the hollow silica particles, the higher the filling rate of the hollow silica particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, relative to 100 parts by mass of the binder resin, the content of the hollow silica particles is preferably 100 parts by mass or more, more preferably 150 parts by mass or more.
[0300] On the other hand, when the content of hollow silica particles relative to the binder resin is too much, the hollow silica particles exposed from the binder resin increase, and the binder resin bound between particles decreases. Therefore, the hollow silica particles are easily damaged or fall off, and there is a tendency that the mechanical strength such as the scratch resistance of the low refractive index layer is reduced. In addition, if the content of the hollow silica particles is too much, there is a tendency that the transfer adaptability is impaired. Therefore, relative to 100 parts by mass of the binder resin, the content of the hollow silica particles is preferably less than 400 parts by mass, more preferably less than 300 parts by mass.
[0301] If the content of non-hollow silica particles is small, even if non-hollow silica particles are present on the surface of the low-refractive index layer, sometimes the hardness rise will not be affected. In addition, if a large amount of non-hollow silica particles are contained, the impact of the uneven shrinkage caused by the polymerization of the binder resin can be reduced, so that the concavo-convex produced on the surface of the low-refractive index layer after the resin is cured can be reduced. Therefore, the content of non-hollow silica particles is preferably more than 90 mass parts relative to 100 mass parts of the binder resin, and more preferably more than 100 mass parts.
[0302] On the other hand, if the content of non-hollow silica particles is too much, non-hollow silica is easily condensed, thereby producing uneven shrinkage of the binder resin, and the surface concavoconvex becomes larger. In addition, if the content of non-hollow silica particles is too much, there is a tendency that transfer adaptability is impaired. Therefore, relative to 100 parts by mass of binder resin, the content of non-hollow silica particles is preferably less than 200 parts by mass, more preferably less than 150 parts by mass.
[0303] By including hollow silica particles and non-hollow silica particles in the binder resin at the above ratio, the barrier properties of the low refractive index layer can be improved. This is presumably because the silica particles are uniformly dispersed at a high filling rate, thereby inhibiting the permeation of gas or the like.
[0304] In addition, various cosmetics such as sunscreen and hand cream sometimes contain low-molecular polymers with low volatility. By making the barrier property of the low refractive index layer good, it is possible to inhibit the low molecular polymer from penetrating into the coating film of the low refractive index layer, thereby inhibiting the undesirable conditions (such as abnormal appearance) caused by the low molecular polymer remaining in the coating film for a long time.
[0305] The binder resin of the low refractive index layer preferably comprises a cured product of an ionizing radiation curable resin composition. In addition, as the ionizing radiation curable compound contained in the ionizing radiation curable resin composition, a compound having an ethylenically unsaturated bond group is preferred. Among them, a (meth)acrylate compound having a (meth)acryloyl group is more preferred.
[0306] Hereinafter, a (meth)acrylate compound having 4 or more ethylenically unsaturated bond groups is referred to as a "multifunctional (meth)acrylate compound". In addition, a (meth)acrylate compound having 2 or more and 3 or less ethylenically unsaturated bond groups is referred to as a "low-functional (meth)acrylate compound".
[0307] As the (meth)acrylate compound, any of a monomer and an oligomer can be used. In particular, in order to suppress uneven shrinkage during curing and to facilitate smoothing of the concavo-convex shape of the low refractive index layer surface, the ionizing radiation curable compound more preferably includes a low-functional (meth)acrylate compound.
[0308] The proportion of the low-functional (meth)acrylate compound in the ionizing radiation-curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass.
[0309] In order to suppress the shrinkage unevenness during curing and to make the unevenness of the surface of the low refractive index layer smooth, the low-functional (meth)acrylate compound is preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.
[0310] Among the (meth)acrylate compounds, examples of bifunctional (meth)acrylate compounds include isocyanuric acid di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, polybutylene glycol di(meth)acrylate and other polyalkylene glycol di(meth)acrylates, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, 1,6-hexanediol diacrylate and the like.
[0311] Examples of the trifunctional (meth)acrylate compound include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.
[0312] Examples of the tetrafunctional or higher polyfunctional (meth)acrylate-based compounds include pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol tetra(meth)acrylate.
[0313] These (meth)acrylate compounds may be modified as described below.
[0314] Examples of the (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.
[0315] Urethane (meth)acrylate can be obtained by reaction of, for example, a polyol and an organic diisocyanate with a hydroxy (meth)acrylate.
[0316] In addition, preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with (meth)acrylic acid, (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with polybasic acids and (meth)acrylic acid, and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with phenols and (meth)acrylic acid.
[0317] In addition, in order to suppress the uneven shrinkage caused by cross-linking and improve the smoothness of the surface, the above-mentioned (meth) acrylate compound can also be a compound modified by modifying a part of the molecular skeleton. For example, as the above-mentioned (meth) acrylate compound, a compound modified by using ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. can also be used. In particular, in order to improve the affinity with low-refractive index particles (silicon dioxide particles therein) and suppress the aggregation of low-refractive index particles, the above-mentioned (meth) acrylate compound is preferably a compound modified by using alkylene oxides such as ethylene oxide and propylene oxide.
[0318] The proportion of the alkylene oxide-modified (meth)acrylate compound in the ionizing radiation curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and most preferably 100% by mass. In addition, the alkylene oxide-modified (meth)acrylate compound is preferably a low-functional (meth)acrylate compound, more preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.
[0319] As the (meth)acrylate compound having two ethylenically unsaturated bond groups obtained by alkylene oxide modification, bisphenol F alkylene oxide modified di(meth)acrylate, bisphenol A alkylene oxide modified di(meth)acrylate, isocyanuric acid alkylene oxide modified di(meth)acrylate and polyalkylene glycol di(meth)acrylate can be cited, among which polyalkylene glycol di(meth)acrylate is preferred. The average repeating unit of the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably 3 or more and 5 or less. In addition, the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably ethylene glycol and / or polyethylene glycol.
[0320] Examples of the (meth)acrylate compound having three ethylenically unsaturated bond groups that has been modified with an alkylene oxide include trimethylolpropane alkylene oxide-modified tri(meth)acrylate and isocyanuric acid alkylene oxide-modified tri(meth)acrylate.
[0321] The above-mentioned ionizing radiation curable resins can be used alone or in combination of two or more.
[0322] The low refractive index layer preferably contains a leveling agent for the purpose of improving antifouling properties and surface smoothness.
[0323] As for the leveling agent, fluorine-based and silicone-based agents can be cited, and silicone-based agents are preferred. By containing a silicone-based leveling agent, the surface of the low reflectivity layer can be made smoother. Furthermore, the sliding property and antifouling property (fingerprint wiping property, large contact angle relative to pure water and hexadecane) of the surface of the low reflectivity layer can be improved.
[0324] The content of the leveling agent is preferably 1 part by mass or more and 25 parts by mass or less, more preferably 2 parts by mass or more and 20 parts by mass or less, and further preferably 5 parts by mass or more and 18 parts by mass or less relative to 100 parts by mass of the binder resin. By making the content of the leveling agent 1 part by mass or more, various properties such as antifouling properties can be easily imparted. In addition, by making the content of the leveling agent 25 parts by mass or less, the reduction of scratch resistance can be suppressed.
[0325] The maximum height roughness Rz of the low refractive index layer is preferably below 110nm, more preferably below 90nm, further preferably below 70nm, and further preferably below 60nm. In addition, Rz / Ra (Ra is the arithmetic mean roughness) is preferably below 12.0, more preferably below 10.0. In the case where Rz is as large as above 90nm and below 110nm, it is particularly effective to set Rz / Ra to the aforementioned range.
[0326] In this specification, Ra and Rz are obtained by expanding the roughness of the two-dimensional roughness parameter described in the Scanning Probe Microscope SPM-9600 Upgrade Kit Operating Instructions (SPM-9600 February 2016, P.194-195) of Shimadzu Corporation into three-dimensional values. Ra and Rz are defined as follows.
[0327] (Arithmetic mean roughness Ra)
[0328] Only the reference length (L) is extracted from the roughness curve in the direction of its average line, the X-axis is taken in the direction of the average line of the extracted part, and the Y-axis is taken in the direction of the longitudinal magnification. The roughness curve is represented by y=f(x). At this time, it is calculated by the following formula.
[0329] [Formula 1]
[0330]
[0331] (Maximum height roughness Rz)
[0332] This value is obtained by extracting only a reference length from the roughness curve in the direction of its average line and measuring the interval between the top line and the bottom line of the valley of the extracted portion in the direction of the longitudinal magnification of the roughness curve.
[0333] When using a scanning probe microscope SPM-9600 manufactured by SHIMADZU CORPORATION, it is preferred to measure and analyze Ra and Rz under the following conditions, for example.
[0334] <Measurement conditions>
[0335] Measurement Mode: Phase
[0336] Scanning range: 5μm×5μm
[0337] Scan speed: 0.8Hz or more and 1Hz or less
[0338] Number of pixels: 512×512
[0339] Cantilever used: Product number “NCHR” of Nano World Holding AG, resonance frequency: 320 kHz, spring constant: 42 N / m
[0340] <Analysis conditions>
[0341] Tilt Correction: Line Fit
[0342] A small Rz means that the convex portion caused by the hollow silica particles in the micro region is small. In addition, a small Rz / Ra means that the concavity and convexity caused by the silica particles in the micro region are uniform and do not have concavities and convexities that are prominent relative to the average altitude difference of the concavity and convexity. In addition, in the present disclosure, the value of Ra is not particularly limited, and Ra is preferably 15 nm or less, more preferably 12 nm or less, further preferably 10 nm or less, and further preferably 6.5 nm or less.
[0343] The above-mentioned ranges of Rz and Rz / Ra can be easily satisfied by uniformly dispersing the low-refractive index particles in the low-refractive index layer or suppressing uneven shrinkage of the low-refractive index layer.
[0344] By making Rz and Rz / Ra on low refractive index layer surface be above-mentioned scope, it is possible to reduce the resistance when solid matter crosses the convex part (by being present in the hollow silica particles near the surface) on low refractive index layer surface. Therefore, it is conceivable that: even if load is applied while rubbing with the gravel with oil content, solid matter also can move smoothly on low refractive index layer surface. In addition, it is considered that the hardness of recess itself has also been improved. As a result, it is possible to infer: prevent the breakage or coming off of hollow silica particles, also prevent the damage of binder resin itself.
[0345] Unless otherwise specified, surface roughness such as Rz and Ra refers to the average value of 14 measurement points excluding the minimum and maximum values among the 16 measurement points.
[0346] In this specification, regarding the above 16 measurement locations, it is preferred that an area 0.5 cm from the outer edge of the measurement sample is used as a blank, and about the area inside the blank, lines are drawn that divide the vertical and horizontal directions into five equal parts, and the 16 intersections at this time are used as the measurement centers. The measurement sample is preferably the same sample as the sample in the above condition 1.
[0347] The surface roughness is a value measured under the conditions of a temperature of 23°C ± 5°C and a relative humidity of 40% RH or more and 65% RH or less. Before each measurement, the target sample is exposed to the above atmosphere for 30 minutes or more, and then measured and evaluated.
[0348] The low refractive index layer can be formed by applying a low refractive index layer to form a coating solution and drying, wherein the low refractive index layer forms a coating solution by dissolving or dispersing the components constituting the low refractive index layer. Usually, in the low refractive index layer forming coating solution, a solvent is used in order to adjust the viscosity or to dissolve or disperse the components.
[0349] Examples of the solvent include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), glycol ethers (1-methoxy-2-propyl acetate, etc.), amides (dimethylformamide, dimethylacetamide, etc.), and mixtures thereof may also be mentioned.
[0350] In the case where the volatilization of the solvent is too fast, when the low refractive index layer is formed with a coating liquid and dried, the solvent is violently convected. Therefore, even if the silicon dioxide particles in the coating liquid are in a uniformly dispersed state, it is also easy to destroy the uniformly dispersed state due to the violent convection of the solvent during drying. Therefore, as a solvent, it is preferred to include a solvent with a slow evaporation rate. Specifically, it is preferred to include a solvent with a relative evaporation rate (relative evaporation rate when the evaporation rate of n-butyl acetate is set to 100) of less than 70, more preferably including a solvent of more than 30 and less than 60. In addition, the relative evaporation rate is preferably more than 10 mass % and less than 50 mass % of all solvents, preferably more than 20 mass % and less than 40 mass %.
[0351] Examples of the relative evaporation rates of solvents having a slow evaporation rate include isobutyl alcohol (64), 1-butanol (47), 1-methoxy-2-propyl acetate (44), ethyl cellosolve (38), and cyclohexanone (32).
[0352] Furthermore, the remaining components of the solvent (solvents other than the solvent with a slow evaporation rate) are preferably excellent in solubility of the resin. In addition, the remaining part of the solvent is preferably a component with a relative evaporation rate of 100 or more.
[0353] In addition, in order to suppress the convection of the solvent during drying and improve the dispersibility of the silica particles, the drying temperature during the formation of the low refractive index layer is preferably as low as possible. The drying temperature can be appropriately set in consideration of the type of solvent, the dispersibility of the silica particles, the production speed, etc.
[0354] <High refractive index layer>
[0355] The refractive index of the high refractive index layer as an example of the functional layer is preferably 1.53 to 1.85, more preferably 1.54 to 1.80, more preferably 1.55 to 1.75, and more preferably 1.56 to 1.70.
[0356] The thickness of the high refractive index layer is preferably 200 nm or less, more preferably 50 nm or more and 180 nm or less, and further preferably 70 nm or more and 150 nm or less. In the case of a high refractive index hard coat layer, the thickness of the hard coat layer is preferably used as a reference.
[0357] The high refractive index layer can be formed, for example, from a high refractive index layer-forming coating liquid containing a binder resin composition and high refractive index particles. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.
[0358] Examples of high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide. The refractive index of antimony pentoxide is about 1.79, the refractive index of zinc oxide is about 1.90, the refractive index of titanium oxide is about 2.3 to 2.7, the refractive index of cerium oxide is about 1.95, the refractive index of tin-doped indium oxide is about 1.95 to 2.00, the refractive index of antimony-doped tin oxide is about 1.75 to 1.85, the refractive index of yttrium oxide is about 1.87, and the refractive index of zirconium oxide is 2.10.
[0359] The average particle diameter of the high refractive index particles is preferably more than 2nm, more preferably more than 5nm, and further preferably more than 10nm. In addition, in order to suppress whitening and achieve transparency, the average particle diameter of the high refractive index particles is preferably less than 200nm, more preferably less than 100nm, more preferably less than 80nm, more preferably less than 60nm, and more preferably less than 30nm. The smaller the average particle diameter of the high refractive index particles, the better the transparency, and in particular, by being set to less than 60nm, the transparency can be made extremely good.
[0360] In the present specification, the average particle size of the high refractive index particles or the low refractive index particles can be calculated by the following operations (y1) to (y3).
[0361] (y1) Photographing a cross section of the high refractive index layer or the low refractive index layer using TEM or STEM The acceleration voltage of TEM or STEM is preferably set to 10 kV or more and 30 kV or less, and the magnification is preferably set to 50,000 or more and 300,000 or less.
[0362] (y2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines in the combination of two straight lines that is the largest when the cross section of the particle is sandwiched between the two straight lines. In the case of particle aggregation, the aggregated particles are measured as one particle.
[0363] (y3) The same operation is performed five times on observation images of the same sample in different screens, and the value obtained by the number average of the particle sizes of 50 particles in total is taken as the average particle size of the high refractive index particles or the low refractive index particles.
[0364] <Anti-glare layer>
[0365] The anti-glare layer, which is an example of the functional layer, has a function of improving the anti-glare property of an adherend.
[0366] The anti-glare layer can be formed from, for example, an anti-glare layer-forming coating liquid containing a binder resin composition and particles. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.
[0367] The particles may be either organic particles or inorganic particles. Examples of organic particles include particles made of polymethyl methacrylate, polyacrylic acid-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine resin, and polyester resin. Examples of inorganic particles include particles made of silicon dioxide, aluminum oxide, antimony, zirconium oxide, and titanium dioxide.
[0368] The average particle size of the particles in the antiglare layer cannot be generally determined because it varies depending on the thickness of the antiglare layer, but is preferably 1.0 μm to 10.0 μm, more preferably 2.0 μm to 8.0 μm, and further preferably 3.0 μm to 6.0 μm.
[0369] The average particle size of the particles in the antiglare layer can be calculated by the following operations (z1) to (z3).
[0370] (z1) Taking a transmission observation image of the cross section of the anti-glare layer using an optical microscope. The magnification is preferably 500 times or more and 2000 times or less.
[0371] (z2) Extract 10 random particles from the observed image and calculate the particle size of each particle. The particle size is measured as the distance between two random parallel straight lines in the combination of two straight lines that is the largest when the cross section of the particle is sandwiched between the two straight lines.
[0372] (z3) The same operation is repeated five times on observation images of different screens of the same sample, and the value obtained by the number average of 50 particle diameters is taken as the average particle diameter of the particles in the antiglare layer.
[0373] The content of particles in the anti-glare layer varies depending on the degree of the target anti-glare property and therefore cannot be generalized; however, it is preferably from 1 part by mass to 100 parts by mass, more preferably from 5 parts by mass to 50 parts by mass, and further preferably from 10 parts by mass to 30 parts by mass, relative to 100 parts by mass of the resin component.
[0374] Furthermore, the anti-glare layer may contain fine particles having an average particle size of less than 500 nm in order to impart antistatic properties, control the refractive index, or adjust the shrinkage of the anti-glare layer caused by curing of the curable resin composition.
[0375] The thickness of the anti-glare layer is preferably 0.5 μm or more, more preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, the thickness of the anti-glare layer is preferably 50 μm or less, more preferably 30 μm or more, more preferably 20 μm or less, more preferably 15 μm or less, and more preferably 10 μm or less. In order to make the bending resistance good, the thickness of the anti-glare layer is preferably 10 μm or less, and more preferably 8 μm or less.
[0376] <Antifouling layer>
[0377] The antifouling layer is preferably formed on the side farthest from the biaxially stretched plastic film for optical use.
[0378] The antifouling layer can be formed, for example, from an antifouling layer-forming coating liquid containing a binder resin composition and an antifouling agent. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.
[0379] Examples of the antifouling agent include fluorine-based resins, silicone-based resins, and fluorine-silicone copolymer resins.
[0380] In order to suppress bleeding from the antifouling layer, the antifouling agent preferably has a reactive group capable of reacting with the binder resin composition. In other words, in the antifouling layer, the antifouling agent is preferably fixed to the binder resin composition.
[0381] In order to suppress bleeding from the antifouling layer, an antifouling agent that can self-crosslink is also preferred. In other words, in the antifouling layer, the antifouling agent is preferably self-crosslinked.
[0382] The content of the antifouling agent in the antifouling layer is preferably 5% by mass or more and 30% by mass or less, and more preferably 7% by mass or more and 20% by mass or less, based on the total solid content of the antifouling layer.
[0383] The thickness of the antifouling layer is not particularly limited. For example, when an antifouling hard coat is formed, the thickness of the hard coat is preferably used as a reference. In addition, when an antifouling low-refractive index layer is formed, the thickness of the low-refractive index layer is preferably used as a reference.
[0384] The haze of the functional film in accordance with JIS K7136:2000 is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less. The haze of the functional film in accordance with JIS K7136:2000 is preferably 0.5% or more, more preferably 1.0% or more, and further preferably 1.5% or more.
[0385] The total light transmittance of the functional film in accordance with JIS K7361-1:1997 is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more.
[0386] <Purpose>
[0387] The biaxially stretched plastic film for optics disclosed in the present invention can be appropriately used as a plastic film for an image display device. As described above, the biaxially stretched plastic film disclosed in the present invention can suppress a black screen when viewed with polarized sunglasses or polarized goggles, and can be particularly suitable for use as an image display device for outdoor use. In addition, when the biaxially stretched plastic film for optics satisfies conditions 3 and 4, the following situation can be suppressed regardless of the direction of bending: after the bending test, the bending tendency remains or the fracture occurs, and therefore, it can be more suitable for use as a plastic film for a curved image display device or a foldable image display device.
[0388] The optical plastic film of the present disclosure can be suitably used as a plastic film disposed on the light emitting surface side of an image display device. In this case, a polarizer is preferably provided between the light source of the image display device and the optical biaxially stretched plastic film of the present disclosure.
[0389] Examples of the plastic film for the image display device include plastic films used as base materials for various functional films such as polarizer protection films, surface protection films, antireflection films, and conductive films constituting touch panels.
[0390] [Polarizing plate]
[0391] The polarizing plate disclosed in the present invention is a polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, and at least one of the first transparent protective plate and the second transparent protective plate is the above-mentioned biaxially stretched plastic film for optical use disclosed in the present invention.
[0392] The polarizing plate is used to provide antireflection properties by combining it with a λ / 4 phase difference plate, for example. In this case, the λ / 4 phase difference plate is arranged on the image display device, and the polarizing plate is arranged on the observer side of the λ / 4 phase difference plate.
[0393] In addition, when the polarizing plate is used for a liquid crystal display device, it is used to give the liquid crystal shutter function. In this case, in the liquid crystal display device, the lower polarizing plate, the liquid crystal layer, and the upper polarizing plate are arranged in this order, and the absorption axis of the polarizer of the lower polarizing plate is arranged perpendicular to the absorption axis of the polarizer of the upper polarizing plate. The polarizer included in the upper polarizing plate is equivalent to the first polarizer.
[0394] The polarizing plate includes a polarizer described below.
[0395] The polarizing plate of the present disclosure uses the optical biaxially stretched plastic film of the present disclosure as at least one of the first transparent protective plate and the second transparent protective plate. In a preferred embodiment, both the first transparent protective plate and the second transparent protective plate are the optical biaxially stretched plastic film of the present disclosure.
[0396] The first transparent protective plate and / or the second transparent protective plate in the polarizing plate of the present disclosure may be a structure in which a functional layer is provided on the biaxially stretched plastic film for optical use of the present disclosure. In other words, the first transparent protective plate and / or the second transparent protective plate in the polarizing plate of the present disclosure may be a functional film in which a functional layer is provided on the biaxially stretched plastic film for optical use of the present disclosure.
[0397] In the case where one of the first transparent protective plate and the second transparent protective plate is the above-mentioned biaxially stretched plastic film for optics disclosed in the present invention, the other transparent protective plate is not particularly limited, but is preferably an optically isotropic transparent protective plate. Optical isotropy means that the in-plane phase difference is less than 20nm, preferably less than 10nm, and more preferably less than 5nm. Regarding transparent substrates with optical isotropy, acrylic film, cyclic olefin film, triacetyl cellulose (TAC) film, etc. can be listed. In addition, when the moisture permeability is close to that of the biaxially stretched plastic film, the polarizing plate can be prevented from being deformed due to water absorption, and the degradation of the polarizer can also be prevented, so acrylic film and cyclic olefin film are preferred.
[0398] When one of the first transparent protective plate and the second transparent protective plate is the above-mentioned biaxially stretched optical plastic film of the present disclosure, it is preferable to use the above-mentioned biaxially stretched optical plastic film of the present disclosure as the transparent protective plate on the light emitting side.
[0399] <Polarizer>
[0400] Examples of polarizers include sheet-type polarizers (polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, ethylene-vinyl acetate copolymer saponified films, etc.) formed by stretching films dyed with iodine or the like, wire grid polarizers composed of a plurality of metal wires arranged in parallel, coating polarizers coated with lyotropic liquid crystal and dichroic guest-host materials, multilayer film polarizers, etc. Furthermore, these polarizers may be reflective polarizers having a function of reflecting non-transmitted polarized light components.
[0401] Regarding the polarizer, it is preferred that the polarization degree is 99.00% or more and the average transmittance is 35% or more, more preferably the polarization degree is 99.90% or more and the average transmittance is 37% or more, and further preferably the polarization degree is 99.95% or more and the average transmittance is 40% or more. In addition, in this specification, the average transmittance refers to the average of the spectral transmittance with a wavelength of 400nm or more and 700nm or less. The wavelength interval for measuring the average transmittance is 5nm.
[0402] The polarizer is preferably disposed so that its absorption axis is substantially parallel to or substantially perpendicular to any one side of the sample of the biaxially stretched plastic film for optical use cut out in the above-mentioned manner.
[0403] [Image display device (1)]
[0404] An image display device (1) disclosed herein comprises: a display element; and a plastic film disposed on the light emitting surface side of the display element, wherein the plastic film is the above-mentioned biaxially stretched plastic film for optical use disclosed herein.
[0405] The optical biaxially stretched plastic film of the present disclosure used in the image display device of the present disclosure may have a functional layer on the optical biaxially stretched plastic film. In other words, the optical biaxially stretched plastic film in the image display device of the present disclosure may be a functional film having a functional layer on the above-mentioned optical biaxially stretched plastic film of the present disclosure. The functional layer is preferably arranged on the side of the optical biaxially stretched plastic film opposite to the display element.
[0406] <Display Components>
[0407] As display elements, liquid crystal display elements, EL display elements (organic EL elements, inorganic EL elements), plasma display elements, etc. can be listed, and further LED display elements such as mini LED and micro LED display elements, liquid crystal display elements or LED display elements using quantum dots can be listed.
[0408] When the display element is a liquid crystal display element, a backlight is required on the surface of the liquid crystal display element opposite to the plastic film.
[0409] Furthermore, the image display device may be an image display device having a touch panel function.
[0410] Examples of the touch panel include a resistive film type, an electrostatic capacitance type, an electromagnetic induction type, an infrared type, and an ultrasonic type.
[0411] Regarding the touch panel function, the function may be added to the display element as in a cell-type touch panel liquid crystal display element, or a touch panel may be mounted on the display element.
[0412] Figure 7 The following are examples of the configuration of an image display device (1) having the biaxially stretched plastic film for optical use and a polarizer disclosed in the present invention and an image display device (2) described later. Figure 7 1A represents a display element, which may be a liquid crystal display element or an organic EL element, etc. In contrast to 1A, 2A is a first polarizer, which is a polarizer attached to the side closest to the observer 30 in the image display device. 3A is a second polarizer, which may be polarized sunglasses, etc.
[0413] Figure 8 is Figure 7 Schematic diagram of an image display device in which a low refractive index layer 40 is further added.
[0414] As for the liquid crystal display element, for example, an active matrix driving type represented by a thin film transistor type, a simple matrix driving type represented by a twisted nematic type and a super twisted nematic type, and the like can be exemplified.
[0415] The biaxially stretched plastic film for optical use disclosed in the present invention can also be suitably applied to an organic EL element. Figure 8 A schematic diagram of an organic EL element is shown.
[0416] Generally, an organic EL element is formed by sequentially stacking a transparent electrode, an organic light-emitting layer, and a metal electrode on a transparent substrate to form a light-emitting body (organic electroluminescent body). Here, the organic light-emitting layer is a laminate of various organic thin films, and it is known that, for example, a laminate of a hole injection layer composed of a triphenylamine derivative and a light-emitting layer composed of a fluorescent organic solid such as anthracene, or a laminate of such a light-emitting layer and an electron injection layer composed of a perylene derivative, or a laminate of these hole injection layers, light-emitting layers, and electron injection layers, etc., have various combinations.
[0417] In an organic EL element, in order to extract the light emitted from the organic light-emitting layer, at least one electrode must be transparent, and a transparent electrode formed of a transparent conductor such as indium tin oxide (ITO) is usually used as the anode. On the other hand, in order to facilitate electron injection and improve the light-emitting efficiency, it is important to use a material with a small work function for the cathode, and a metal electrode such as Mg-Ag or Al-Li is usually used.
[0418] In an organic EL element of this structure, the organic light-emitting layer is formed of an extremely thin film with a thickness of about 10 nm. Therefore, the organic light-emitting layer also transmits light almost completely, just like the transparent electrode. As a result, light that is incident from the surface of the transparent substrate, passes through the transparent electrode and the organic light-emitting layer, and is reflected by the metal electrode in the non-luminescent state is emitted again to the surface side of the transparent substrate, so that when observed from the outside, the display surface of the organic EL display device looks like a mirror surface.
[0419] However, if a birefringent layer such as a λ / 4 phase difference plate (not shown) is combined with a polarizer (first polarizer) and the angle between the polarization directions of the polarizer and the birefringent layer is adjusted to π / 4, the mirror surface of the metal electrode can be completely shielded.
[0420] That is, for the external light incident on the organic EL display device, only the linear polarization component is transmitted due to the polarizer. The linear polarization usually becomes elliptically polarized light through the birefringent layer, but when the birefringent layer is a λ / 4 phase difference plate and the angle between the birefringent layer and the polarization direction of the polarizer is π / 4, it becomes circularly polarized light. The circularly polarized light passes through the transparent substrate, the transparent electrode, and the organic film, is reflected by the metal electrode, passes through the organic film, the transparent electrode, and the transparent substrate again, and becomes linearly polarized light again through the λ / 4 phase difference plate. Then, the linear polarization cannot pass through the polarizer because it is perpendicular to the polarization direction of the polarizer. As a result, the mirror surface of the metal electrode can be completely shielded.
[0421] This 2A is a polarizer (first polarizer), and is a polarizer in the image display device that is attached to the side closest to the viewer.
[0422] The optical biaxially stretched plastic film disclosed in the present invention is disposed in an image display device between the first polarizer and polarized sunglasses 3A (second polarizer). The optical biaxially stretched plastic film and the first polarizer may be laminated via an adhesive layer (not shown. The same shall apply hereinafter).
[0423] As the adhesive used in the adhesive layer of the present disclosure, there is no particular limitation, for example, an adhesive with polymers such as acrylic acid polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluorine-based and rubber-based polymers as base polymers can be appropriately selected and used. For the adhesive, it is required to have excellent adhesive properties such as optical transparency, appropriate wettability, cohesiveness, adhesion, weather resistance, heat resistance, etc. Furthermore, from the aspects of preventing the foaming phenomenon and peeling phenomenon caused by moisture absorption, preventing the reduction of optical properties caused by thermal expansion difference, etc. and the warping of liquid crystal cells, and then forming an image display device with excellent durability with high quality, it is required that the adhesive layer with low moisture absorption rate and excellent heat resistance. In order to meet these requirements, acrylic acid adhesives are preferred.
[0424] The adhesive may contain additives such as natural resins, synthetic resins, tackifying resins, glass fibers, glass beads, metal powders, pigments, colorants, antioxidants, etc. In addition, the adhesive layer may contain fine particles to exhibit light diffusivity.
[0425] The application of the above-mentioned adhesive to the polarizing plate of the present disclosure is not particularly limited and can be carried out by an appropriate method. For example, the following methods can be cited: preparing an adhesive solution of about 10% by mass or more and about 40% by mass or less by mass by dissolving or dispersing a base polymer or its components in a solvent consisting of a single substance or a mixture of an appropriate solvent such as toluene and ethyl acetate, and directly applying the adhesive solution to the polarizing plate of the present disclosure by an appropriate development method such as a casting method and a coating method; or forming an adhesive layer on a releasable base film according to the method and transferring it to the polarizing plate of the present disclosure.
[0426] The coating method may be various methods such as gravure coating, rod coating, roll coating, reverse roll coating, comma coating, etc., and the most common one is gravure coating.
[0427] The adhesive layer may also be provided on one or both sides of the polarizing plate of the present disclosure as a superimposed layer of adhesive layers of different components or types. In addition, when provided on both sides, the adhesives on the front and back sides of the polarizing plate of the present disclosure do not need to be of the same component, and do not need to be of the same thickness. Adhesive layers of different components and different thicknesses may also be used.
[0428] The thickness of the adhesive layer can be appropriately determined depending on the intended use, adhesive strength, etc., and is usually 1 μm to 500 μm, preferably 5 μm to 200 μm, and particularly preferably 10 μm to 100 μm.
[0429] <Other plastic films>
[0430] The image display device of the present disclosure may have other plastic films within a range not impairing the effects of the present disclosure.
[0431] As the other plastic film, a plastic film having optical isotropy is preferred.
[0432] Examples of the plastic film disposed on the light emitting surface side of the display element include plastic films used as substrates of various functional films such as polarizer protection films, surface protection films, antireflection films, and conductive films constituting touch panels.
[0433] [Image display device (2)]
[0434] <Condition 1B>
[0435] The luminance difference (L1.n-L2.n) between the luminance obtained in the following measurement 1B and the luminance obtained in the following measurement 2B is calculated at 100 measurement points, and the "luminance difference deviation 3σ" calculated from the luminance difference at the 100 measurement points is 100 or more.
[0436] Measurement 1B
[0437] A 1B measurement sample is prepared in which the first polarizer, the optical biaxially stretched plastic film, and the second polarizer are arranged in this order on the display element. In the 1B measurement sample, the direction of the slow axis of the optical biaxially stretched plastic film is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer, and the absorption axis of the second polarizer is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer.
[0438] Make the display element of the 1B measurement sample display white, measure the brightness of the transmitted light emitted from the second polarizer side at measurement points of 100×100 set at equal intervals in any first area, extract any 100 points in a horizontal column from the measurement results, and use them as the 1st to 100th measurement points, respectively, define the brightness of the 1st measurement point as L1.1, the brightness of the 100th measurement point as L1.100, and the brightness of the nth measurement point as L1.n.
[0439] Measurement 2B
[0440] A measurement sample 2B is prepared on the same display element as measurement sample 1B, in which the first polarizer and the second polarizer are arranged in this order. In the measurement sample 2B, the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer.
[0441] Make the display element of the 2B measurement sample display white, measure the brightness of the transmitted light emitted from the second polarizer side at 100×100 measurement points set at equal intervals in the area roughly consistent with the first measurement area, extract any 100 points in a horizontal column from the measurement results, and use them as the 1st to 100th measurement points, respectively, define the brightness of the 1st measurement point as L2.1, the brightness of the 100th measurement point as L2.100, and the brightness of the nth measurement point as L2.n.
[0442] <Condition 2B>
[0443] The in-plane retardation (Re) is 2500 nm or less.
[0444] The image display device (2) disclosed in the present invention is an image display device having the first polarizer and an optical biaxially stretched plastic film on the light emitting surface of the display element, wherein the image display device is configured so that the direction of the slow axis of the optical biaxially stretched plastic film is approximately perpendicular to the direction of the absorption axis of the first polarizer, and the optical biaxially stretched plastic film has an area that satisfies the <Condition 1B> and the <Condition 2B>.
[0445] The "1B measurement sample" in the measurement 1B of the image display device (2) refers to a sample in which a second polarizer is arranged on the light exit surface of the image display device (2). In addition, the "2B measurement sample" in the measurement 2B of the image display device (2) refers to a sample in which the optical biaxially stretched plastic film of the present disclosure described above is removed from the image display device (2) and a second polarizer is arranged on the light exit surface side of the first polarizer.
[0446] Measurement 1B and Measurement 2B in the image display device (2) of the present disclosure are the same as the above-mentioned Measurement 1 and Measurement 2 of the biaxially stretched plastic film for optical use of the present disclosure, except that the surface light source and the display element are different.
[0447] In addition, the preferred embodiments of measurement 1B and measurement 2B are the same as the preferred embodiments of measurement 1 and measurement 2 (for example, the preferred range of the brightness of the transmitted light emitted from the first polarizer side when the first polarizer is arranged on the display element is the same as the preferred range of the brightness of the transmitted light emitted from the first polarizer side when the first polarizer is arranged on the surface light source). In addition, the preferred embodiments of condition 1B and condition 2B are the same as the preferred embodiments of condition 1 and condition 2 described above.
[0448] <Application of Image Display Device>
[0449] The image display device disclosed herein is an image display device including a display element and an optical biaxially stretched plastic film disposed on the light emitting surface side of the display element.
[0450] The image display device disclosed in the present invention may be an image display device for use indoors or outdoors, but is preferably an image display device for use outdoors in an environment where an observer uses polarized sunglasses or polarized goggles.
[0451] Specifically, it is preferably used for tablet computers, smart phones, smart watches and other clocks, car navigation, PID (public information display), fish finders or drone operation screens. In the case of movable image display devices such as tablet computers and smart phones, since the conditions of external light and the position of the observer and the light emitting surface change, it is preferred to use the optical biaxially stretched plastic film of the present invention, which is less likely to produce a black screen. In addition, in the case of a fixed image display element device such as PID, although the image display device does not move, in order to allow the observer to watch the image display device while moving, it is required that a black screen does not appear at a larger viewing angle, and it is preferred to use the optical biaxially stretched plastic film disclosed in the present invention and a functional film using the biaxially stretched plastic film.
[0452] In addition, as described above, the optical biaxially stretched plastic film disclosed in the present invention can suppress the following situations: after the bending test, the bending tendency remains or the fracture occurs. Therefore, regarding the image display device disclosed in the present invention, in the case of a curved image display device or a foldable image display device, it is preferred in that a more significant effect can be exerted.
[0453] Furthermore, when the image display device is a curved image display device or a foldable image display device, the image display device is preferably an organic EL element.
[0454] <Relationship between the absorption axis of the polarizing plate and the slow axis of the optical plastic>
[0455] The second polarizer is equivalent to a lens such as polarized sunglasses or polarized goggles. For example, in the case of polarized sunglasses, in order to absorb reflected light from a horizontal surface such as a water surface, the absorption axis becomes a horizontal direction. The slow axis of the optical biaxially stretched plastic film disclosed in the present invention is preferably parallel to the absorption axis of the second polarizer, that is, horizontal or approximately horizontal relative to the ground. Furthermore, in the case where the absorption axis of the first polarizer is perpendicular or approximately perpendicular to the absorption axis of the second polarizer, the effect of the present invention is maximized, and therefore it is preferred. The vertically long image display device for PID is obtained by rotating the horizontally long image display device for television by 90 degrees, so the absorption axes of the first polarizer of the image display device for PID and the image display device for television mostly differ by 90 degrees. Therefore, especially in the case where the absorption axes of the first polarizer and the second polarizer are perpendicular or approximately perpendicular, the effect of the present invention is maximized, and therefore it is preferred.
[0456] Furthermore, when the direction of the slow axis is non-uniform in the plane of the biaxially stretched optical plastic film, the direction of the slow axis of the biaxially stretched optical plastic film means the average direction of the slow axis of the biaxially stretched optical plastic film.
[0457] [Selection method of biaxially stretched plastic film for optical use]
[0458] The method for selecting a biaxially stretched plastic film for an optical purpose in an image display device disclosed herein is a method for selecting a biaxially stretched plastic film for an optical purpose in an image display device having a polarizing plate and a biaxially stretched plastic film for an optical purpose on a surface on the light emitting surface side of the image display device, wherein a region satisfying condition 1 and condition 2 is used as a determination condition, and a biaxially stretched plastic film satisfying the determination condition is selected as the biaxially stretched plastic film for an optical purpose.
[0459] Conditions 1 and 2 are the above-mentioned conditions. The method for selecting a biaxially stretched plastic film for optical use in an image display device disclosed in the present invention preferably further comprises an additional determination condition as a determination condition. As the additional determination condition, preferred embodiments of the biaxially stretched plastic film for optical use disclosed in the present invention (for example, embodiments satisfying condition 3 and / or condition 4, etc.) can be listed.
[0460] According to the method for selecting an optical film for a display device disclosed in the present disclosure, an optical film that can suppress a black screen when viewed through polarized sunglasses can be efficiently selected, thereby improving workability.
[0461] Example
[0462] Next, the present disclosure will be described in more detail by way of examples, but the present disclosure is not limited to these examples at all.
[0463] 1. Measurement and evaluation
[0464] The following measurement and evaluation were performed under an atmosphere of 23° C.±5° C. and a relative humidity of 40% RH or more and 65% RH or less. In addition, the sample was exposed to the atmosphere for 30 minutes or more before the measurement and evaluation.
[0465] 1-1. Brightness
[0466] A measurement sample of 120 mm in length×120 mm in width was cut out from a biaxially stretched plastic film for optical use.
[0467] The surface light source described later, the first polarizer (hereinafter, the polarizer uses the product "MUHD40S, polarization degree 99.97%, average transmittance 40.0%" of Me Can Imaging Inc.), the cut biaxially stretched plastic film, and the second polarizer are sequentially overlapped to prepare the first measurement sample. The slow axis direction of the optical biaxially stretched plastic film is arranged to be perpendicular to the absorption axis direction of the first polarizer, and the absorption axis of the second polarizer is arranged to be perpendicular to the absorption axis direction of the first polarizer.
[0468] The surface light source of the first measurement sample was made to display white.
[0469] The measurement device used was a product of Cybernet Corporation, product number "Prometric PM1423-1, imaging luminance meter, CCD resolution: 1536×1024". Figure 1 The first measurement sample and the imaging luminance meter are set at a positional relationship of . The distance between the camera and the surface light source is set to 750 mm.
[0470] A region of 100 mm in length by 100 mm in width within 10 mm in the top, bottom, left, and right directions from the outline of the cut biaxially stretched plastic film in the first measurement sample is used as the measurement region.
[0471] Next, the following “settings before measurement” and “adjustment of exposure time” were performed, and then the following “measurement and analysis” was performed. The measurement was performed in a darkroom environment.
[0472] <Settings before measurement>
[0473] (1) Connect the imaging luminance meter to a personal computer and start the attached software (RADIANT IMAGING Prometric 9.1 Version 9.1.32) of the imaging luminance meter in the personal computer.
[0474] (2) When the software is started, the CCD temperature in the imaging luminance meter is automatically adjusted to blue display (-10°C). Wait until the CCD temperature stabilizes at -10°C.
[0475] (3) In the "Measurement Settings" of the software, specify "Color, 1x1 binning".
[0476] (4) Set the lens aperture dial to 1.8 and bring the second polarizer into focus.
[0477] <Adjustment of exposure time>
[0478] Implement the "Exposure Time Adjustment" of the software. Specifically, press "Adjust" in the order of Y (green), X (red), and Z (blue), and then save. Implement the exposure time adjustment every time you measure a sample.
[0479] <Measurement and Analysis>
[0480] Select "Focus mode" from the tool bar and confirm that the measurement target area is reflected in the focus mode image.
[0481] Press "Execute measurement" to carry out the measurement. Save the measurement result.
[0482] Select "Tools" and "Measurement Data Processing" from the tool bar. Next, select "Cut Range" from the pull-down menu of "Select Processing Contents". Next, specify a range of 100 mm x 100 mm of the sample and save it. The saved data is referred to as "Saved Data 1".
[0483] Open saved data 1. Next, select "Tools" and "Export of measurement data" from the tool bar. Next, select "Brightness" as the data type, set the resolution to "X: 100, Y: 100", and set the output format to "XY Table", and export the Excel data.
[0484] Through the above steps, the brightness data of 100×100 measurement points are obtained. By extracting 100 points in any horizontal row from the measurement results, we can obtain Figure 3 Luminance data of 100 points are shown (L1.n. Luminance of measurement 1).
[0485] Furthermore, in measurement 1, measurement points whose brightness changes by more than 30% relative to adjacent measurement points are excluded from the measurement results as measurement points due to local defects of the member constituting the first measurement sample. The same applies to measurement 2 described later.
[0486] As the surface light source, the following three types of surface light sources were used.
[0487] The brightness described below is an average value of the brightness obtained at 100 measurement points under the condition where the second polarizer is further removed from the measurement of Measurement 2, and 3σ of the brightness is calculated from the brightness at the obtained 100 points.
[0488] The color temperature of the surface light source was measured using a device with the product number "Prometric PM1423-1, imaging luminance meter, CCD resolution: 1536×1024" from Cybernet. Regarding the data of the color temperature of the surface light source, it can be obtained in the same way as the above luminance measurement, except that the type of the exported data is changed from "luminance" to "correlated color temperature". Then, the average value of the color temperatures at four positions advancing 10 mm from the four corners of the 100 mm×100 mm measurement area towards the central part and the central part of the sample, a total of five positions, is taken as the color temperature of each surface light source.
[0489] <LED light source (LED)>
[0490] LED light source: A product with the trade name "Dbmier A4S" from GraphicsPower, thin type 4.5 mm, USB powered (278×372×4.5 mm), was used as the surface light source.
[0491] Luminance: 23021, 3σ of luminance: 6917, color temperature of white display: 10526K
[0492] <OLED for RGB display (OLED)>
[0493] The structure obtained by removing the polarizing element from a product with the trade name "galaxy Note4" from Samsung was used for white display as the surface light source.
[0494] Luminance: 32995, 3σ of luminance: 2433, color temperature of white display: 6962K
[0495] <LCD monitor (LCD)>
[0496] The structure obtained by removing the outermost polarizing element of the display element from a product with the trade name "EV2450Z" from EIZO was used for white display as the surface light source.
[0497] Luminance: 36907, 3σ of luminance: 1564, color temperature of white display: 7772K
[0498] Except for removing the optically biaxially stretched plastic film, Measurement 2 was carried out in the same way as Measurement 1, and the luminance (L2.n, luminance of Measurement 2) was measured. And the second measurement area as the measurement area of Measurement 2 was made to be roughly the same as the first measurement area as the measurement area of Measurement 1.
[0499] 1-2. Calculation of "deviation 3σ of luminance difference"
[0500] Using the brightness L1.n and L2.n of the 100 points measured, the brightness difference (L1.n-L2.n) is calculated. The negative values in the brightness difference of the 100 points are removed, and the "brightness difference deviation 3σ" is calculated. Since the first polarizer and the second polarizer are configured in the form of orthogonal Nicol prisms, the brightness of L2.n is usually low. The measurement point with a negative brightness difference can be said to be an abnormal point where L2.n shows a higher value due to local light leakage from the orthogonal Nicol prism, so it is excluded from the calculation of 3σ.
[0501] In addition, in both the example and the comparative example, the number of luminance measurement points used when calculating the luminance difference deviation 3σ was 80 or more.
[0502] 1-2. In-plane phase difference (Re), thickness direction phase difference (Rth), and deviation of slow axis
[0503] A measurement sample of 100 mm in length and 100 mm in width is cut out from a biaxially stretched plastic film for optical use. The conveying direction (MD direction) of the measurement sample is regarded as the longitudinal direction, and the width direction (TD direction) of the plastic film is regarded as the transverse direction. The in-plane phase difference, the phase difference in the thickness direction, and the direction of the slow axis are measured for the four locations, which are 10 mm from the four corners of the sample toward the center, and the central part of the sample, a total of five locations. Table 1 shows the average of Re1 to Re5 calculated from the measurement results. The measuring device uses a device with the trade name "RETS-100 (measuring point: diameter 5 mm)" of Otsuka Electronics Co., Ltd. In addition, regarding the direction of the slow axis, the measurement was performed in the range of more than 0 degrees and less than 90 degrees, with the conveying direction (MD direction) of the plastic film as the reference of 0 degrees.
[0504] 1-3. Black screen evaluation
[0505] The black screen was evaluated by evaluating the readability of 18-point characters in a bright room environment where the image display device was powered off and the surface brightness of the image display device was 300 lux or more and 750 lux or less.
[0506] Turn on the power of the image display device, and display 18-point text in black on a white background. Twenty evaluators (5 selected from each age group of approximately 20 years old, approximately 30 years old, approximately 40 years old, and approximately 50 years old) observed from a distance of about 750 mm from the image display device to evaluate whether the text could be recognized. The line of sight of the evaluator was at the same height as the image display device. In addition, the position of the evaluator was set in the front direction of the image display device. The case where 15 or more and 20 or fewer people could recognize was set as "A", the case where 10 or more and 14 or fewer people could recognize was set as "B", and the case where 9 or fewer people could recognize was set as "C".
[0507] 1-4. Flexural resistance
[0508]
[0509] Cut out a long strip-shaped sample with a short side (TD direction) of 30 mm × a long side (MD direction) of 100 mm from the optically biaxially stretched plastic film. Fix both ends of the short side (30 mm) side of the sample (fix the area 10 mm from the end) to a durability test machine (product name: "DLDMLH-FS", YUASA SYSTEM CO., LTD.), and perform a continuous folding test of folding 180 degrees 100,000 times. The folding speed is 120 times per minute. The more detailed method of the folding test is as follows. The average direction of the TD direction is substantially the same as the direction of the slow axis.
[0510] After the folding test, place the long strip-shaped sample on a horizontal table, and measure the angle at which the end of the sample翘翘 from the table. The results are shown in Table 1. And the case where the sample breaks midway is set as "broken".
[0511] <MD direction>
[0512] Cut out a long strip-shaped sample with a short side (MD direction) of 30 mm × a long side (TD direction) of 100 mm from the optically biaxially stretched plastic film, and perform the same evaluation as above.
[0513] <Details of the folding test>
[0514] As Figure 6 shown in (A) of, in the continuous folding test, first, fix the side portion 10C of the plastic film 10 and the side portion 10D opposite to the side portion 10C respectively with the parallelly arranged fixing portions 60. The fixing portions 60 can slide horizontally.
[0515] Next, as Figure 6 shown in (B) of, by moving the fixing portions 60 closer to each other, the plastic film 10 is deformed in a folded manner. Furthermore, as Figure 6As shown in (C), after the fixing part 60 is moved to a position where the interval between two opposing sides of the plastic film 10 fixed by the fixing part 60 becomes 10 mm, the fixing part 60 is moved in the reverse direction to eliminate the deformation of the plastic film 10.
[0516] Through Figure 6 The plastic film 10 can be folded 180 degrees by moving the fixing part 60 as shown in (A) to (C). In addition, the continuous folding test is performed in a manner that the curved part 10E of the plastic film 10 does not protrude from the lower end of the fixing part 60, and the interval when the fixing part 60 is closest is controlled to 10 mm, thereby making it possible to make the interval between the two opposing sides of the optical film 10 10 mm.
[0517] [Examples 1 to 3]
[0518] 1 kg of PET (melting point: 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinone-4-one) were melt-mixed at 280°C in a kneader to prepare pellets containing the ultraviolet absorber. The pellets and PET having a melting point of 258°C were put into a single screw extruder and melt-mixed at 280°C, extruded from a T-die, and cast on a casting drum whose surface temperature was controlled to 25°C to obtain a cast film. The amount of the ultraviolet absorber in the cast film was 1 part by mass relative to 100 parts by mass of PET.
[0519] After the obtained cast film was heated by a roller set at 95°C, the film was stretched 3.3 times in the conveying direction while heating both the front and back sides of the film by a radiation heater so that the film temperature at a point of 250 mm in a 400 mm stretching section (starting point is stretching roller A, end point is stretching roller B, and stretching rollers A and B each have two press rollers) was 103°C, and then temporarily cooled. In addition, when heating by the radiation heater, a wind of 92°C and 4 m / s was blown to the film from the side of the radiation heater opposite to the film, thereby generating turbulence on the front and back sides of the film, and disturbing the temperature uniformity of the film.
[0520] Next, both surfaces of the uniaxially stretched film were subjected to corona discharge treatment in air so that the wetting tension of the base film was 55 mN / m, and a "lubricating layer coating liquid comprising a polyester resin having a glass transition temperature of 18°C, a polyester resin having a glass transition temperature of 82°C, and silica particles having an average particle size of 100 nm" was applied online to the corona discharge treated surfaces of both surfaces of the film to form an lubricating layer.
[0521] Next, the uniaxially stretched film was introduced into a tenter, and after being preheated with hot air at 95°C, it was stretched 4.5 times in the width direction of the film at a temperature of 105°C in the first stage and 140°C in the second stage. Here, when the transverse stretching section was divided into two equal parts, the film was stretched in two stages so that the stretching amount of the film at the middle point of the transverse stretching section (film width at the measuring point - film width before stretching) became 80% of the stretching amount at the end of the transverse stretching section. The film after transverse stretching was heat-treated in stages in the tenter using hot air from 180°C to 245°C, which is a heat treatment temperature, and then a 1% relaxation treatment was performed in the width direction under the same temperature conditions. After further rapid cooling to 100°C, a 1% relaxation treatment was performed in the width direction, and then it was wound up to obtain a biaxially stretched polyester film 1 (biaxially stretched polyester film used in Examples 1 to 3) having a thickness of 40 μm.
[0522] Table 1 summarizes the physical property values of the obtained biaxially stretched polyester film 1 and the evaluations of “variation in brightness difference” and “black screen evaluation (readability)” when the above three types of surface light sources were used.
[0523] [Table 1]
[0524] Table 1
[0525]
[0526] The readability of the biaxially stretched polyester film of the example was good regardless of the surface light source. In addition, the biaxially stretched polyester film 1 had good bending resistance.
[0527] [Comparative Examples 1 to 8]
[0528] The black screen (readability) was evaluated in the same manner as in Example 1 except that the following comparative films 1 to 3 were used as the polyester film. The surface light sources described in Tables 2 to 4 were used as the surface light sources. The results are shown in Tables 2 to 4.
[0529] <Comparative Film 1>
[0530] The product name of Toyobo Co., Ltd. is "Cosmoshine A4300, biaxially stretched polyester film" (film thickness: 188 μm, average Re: 8259 nm)
[0531] <Comparative Film 2>
[0532] The product name of Toyobo Co., Ltd. is "Cosmoshine TA048, uniaxially stretched film" (film thickness: 80 μm, average Re: 10302 nm)
[0533] <Comparative Film 3>
[0534] The product name of Toyobo Co., Ltd. is "Cosmoshine A4300, biaxially stretched polyester film" (film thickness: 100 μm, average Re of 4207 nm)
[0535] [Table 2]
[0536] Table 2
[0537] Comparative Example 1 Comparative Example 2 Biaxially stretched film Comparison film 1 Comparison film 2 Area light source led led Average brightness 59 34 Condition 1: Brightness difference deviation 3σ 49 65 Black screen evaluation (readability) C C
[0538] [Table 3]
[0539] Table 3
[0540] Comparative Example 3 Comparative Example 4 Comparative Example 5 Biaxially stretched film Comparison film 1 Comparison film 2 Comparison film 3 Area light source oLED oLED oLED Average brightness 24 48 72 Condition 1: Brightness difference deviation 3σ 79 38 95 Black screen evaluation (readability) C C C
[0541] [Table 4]
[0542] Table 4
[0543] Comparative Example 6 Comparative Example 7 Comparative Example 8 Biaxially stretched film Comparison film 1 Comparison film 2 Comparison film 3 Area light source LCD LCD LCD Average brightness 10 16 31 Condition 1: Brightness difference deviation 3σ 52 28 77 Black screen evaluation (readability) C C C
[0544] In Comparative Examples 1 to 8, readability was low and black screens occurred in all of them.
[0545] [Example 4]
[0546] A functional film of Example 4 was prepared in which a low refractive index layer having a reflectivity of 0.15% was further laminated on the optical biaxially stretched plastic film of Example 1 as a functional layer. The "brightness difference deviation 3σ" and black screen evaluation were performed in the same manner as in Example 1, except that the functional film of Example 4 was used instead of the optical biaxially stretched plastic film of Example 1. The surface light source described in Table 5 was used as the surface light source. The results are shown in Table 5.
[0547] [Table 5]
[0548] Table 5
[0549] Example 4 Area light source led Average brightness 186 Condition 1: Brightness difference deviation 3σ 153 Black screen evaluation (readability) A
[0550] As shown in Table 5, the functional film of Example 4 showed good readability.
[0551] In addition, even when the reflectance of the low refractive index layer of Example 4 was changed to 0.65%, 1.00%, or 1.65%, the readability was as good as that of Example 4.
[0552] [Examples 5 to 7]
[0553] The biaxially stretched polyester film 2 used in Examples 5 to 7 was obtained in the same manner as the biaxially stretched polyester film 1 except that the stretching ratio in the width direction was changed from 4.5 times to 4.9 times.
[0554] Table 6 summarizes the physical property values of the obtained biaxially stretched polyester film 2, as well as the evaluation of "variation in brightness difference" and "black screen evaluation (readability)" when the above-mentioned three types of surface light sources were used.
[0555] [Table 6]
[0556] Table 6
[0557]
[0558] As shown in Table 6, in Examples 5 to 7, readability was good regardless of the surface light source. In addition, the biaxially stretched polyester film 2 had good bending resistance.
[0559] [Reference Examples 1-2]
[0560] As the optical plastic film of Reference Example 1, a commercially available biaxially stretched polyester film (Toyobo Co., Ltd., trade name: Cosmoshine A4100, thickness: 50 μm, average Re: 2202 nm) was prepared.
[0561] As the optical plastic film of Reference Example 2, a commercially available uniaxially stretched polyester film (Toyobo Co., Ltd., trade name: Cosmoshine TA048, thickness: 80 μm) was prepared.
[0562] The bending resistance was evaluated in the same manner as in the examples using the polyester films of Reference Examples 1 and 2. The results are shown in Table 7.
[0563] [Table 7]
[0564] Table 7
[0565]
[0566] From the results of Table 7, it can be confirmed that the biaxially stretched polyester film of the example has better bending resistance than the uniaxially stretched polyester film and the general biaxially stretched film.
[0567] Description of symbols
[0568] 1: Surface light source;
[0569] 1A: Display element;
[0570] 2: 1st polarizer;
[0571] 2A: the polarizer closest to the observer (the first polarizer);
[0572] 3: Second polarizer;
[0573] 3A: Polarized sunglasses (2nd polarizer);
[0574] 4: 1st measurement sample;
[0575] 5: 2nd measurement sample;
[0576] 10: Biaxially stretched plastic film for optics;
[0577] 10C: The edge of the biaxially stretched plastic film 10 for optical use;
[0578] 10D: The edge corresponding to 10C;
[0579] 10E: curved portion of the biaxially stretched plastic film 10 for optical use;
[0580] 20: Imaging luminance meter;
[0581] 21: 1st measurement sample;
[0582] 22: 2nd 1st measurement sample;
[0583] 23: 3rd 1st measurement sample;
[0584] 24: diagonal;
[0585] 30: Observer;
[0586] 40: low refractive index layer;
[0587] 60: fixing parts arranged parallel to each other;
[0588] Re1~5: Measurement points of condition 2.
Claims
1. A biaxially stretched plastic film for optical use, wherein: The biaxially stretched plastic film for optical use has a region satisfying conditions 1 and 2, Condition 1 The brightness difference between the brightness obtained in the following measurement 1 and the brightness obtained in the following measurement 2, i.e., L1.n-L2.n, is calculated at 100 measurement points, and the "brightness difference deviation 3σ" calculated from the brightness difference at the 100 measurement points is 100 or more, Measurement 1 A first measurement sample is prepared in which a first polarizer, an optical biaxially stretched plastic film, and a second polarizer are arranged in this order on a surface light source. In the first measurement sample, the direction of the slow axis of the optical biaxially stretched plastic film is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer, and the absorption axis of the second polarizer is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer. The surface light source of the first measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at measurement points of 100×100 set at equal intervals in the vertical and horizontal directions in an arbitrary first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L1.1, the brightness of the 100th measurement point is defined as L1.100, and the brightness of the nth measurement point is defined as L1.n, Measurement 2 A second measurement sample is prepared in which the first polarizer and the second polarizer are arranged in this order on the same surface light source as the measurement 1, wherein in the second measurement sample, the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer. The surface light source of the second measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at 100×100 measurement points set at equal intervals in the vertical and horizontal directions in an area substantially consistent with the first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L2.1, the brightness of the 100th measurement point is defined as L2.100, and the brightness of the nth measurement point is defined as L2.n; Condition 2 The in-plane phase difference Re is 2500 nm or less.
2. The biaxially stretched plastic film for optical use according to claim 1, wherein The in-plane phase difference with respect to the phase difference in the thickness direction is 0.10 or less.
3. The biaxially stretched plastic film for optical use according to claim 1, wherein The film thickness of the biaxially stretched plastic film for optical use is 20 μm or more and 200 μm or less.
4. A functional film, wherein: The functional film is a film obtained by providing a functional layer on one surface of the biaxially stretched plastic film for optical use according to any one of claims 1 to 3.
5. A polarizing plate comprising a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein: At least one of the first transparent protective plate and the second transparent protective plate is the biaxially stretched plastic film for optical use according to any one of claims 1 to 3.
6. An image display device comprising a display element and a plastic film disposed on a light emitting surface side of the display element, wherein: The plastic film is the biaxially stretched plastic film for optical use according to any one of claims 1 to 3.
7. The image display device according to claim 6, wherein: A polarizer is provided between the display element and the plastic film.
8. The image display device according to claim 6 or 7, wherein: The optical biaxially stretched plastic film further has a functional layer on the side opposite to the display element.
9. An image display device comprising a first polarizer and an optical biaxially stretched plastic film on a light emitting surface of a display element, wherein: The image display device is configured such that the slow axis of the optical biaxially stretched plastic film is substantially perpendicular to the absorption axis of the first polarizer, and the optical biaxially stretched plastic film has a region satisfying conditions 1B and 2B. Condition 1B The brightness difference between the brightness obtained in the following measurement 1B and the brightness obtained in the following measurement 2B, i.e., L1.n-L2.n, is calculated at 100 measurement points, and the "brightness difference deviation 3σ" calculated from the brightness difference at the 100 measurement points is 100 or more, Measurement 1B A 1B measurement sample is prepared in which the first polarizer, the optical biaxially stretched plastic film, and the second polarizer are arranged in this order on the display element, wherein in the 1B measurement sample, the slow axis of the optical biaxially stretched plastic film is arranged to be approximately perpendicular to the absorption axis of the first polarizer, and the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer. The display element of the 1B measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at measurement points of 100×100 set at equal intervals in the vertical and horizontal directions in an arbitrary first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L1.1, the brightness of the 100th measurement point is defined as L1.100, and the brightness of the nth measurement point is defined as L1.n, Measurement 2B A measurement sample 2B is prepared on the same display element as the measurement sample 1B, in which the first polarizer and the second polarizer are arranged in this order. In the measurement sample 2B, the absorption axis of the second polarizer is arranged to be substantially perpendicular to the absorption axis of the first polarizer. The display element of the 2B measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at 100×100 measurement points set at equal intervals in the vertical and horizontal directions in an area substantially consistent with the first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L2.1, the brightness of the 100th measurement point is defined as L2.100, and the brightness of the nth measurement point is defined as L2.n; Condition 2B The in-plane phase difference Re is 2500 nm or less.
10. A method for selecting a biaxially stretched plastic film for optical use, which is a method for selecting a biaxially stretched plastic film for an image display device having the biaxially stretched plastic film for optical use on the light emitting surface side of a display element, wherein: A region satisfying condition 1 and condition 2 is used as a determination condition, and a biaxially stretched plastic film satisfying the determination condition is selected as a biaxially stretched plastic film for optical use. Condition 1 The brightness difference between the brightness obtained in the following measurement 1 and the brightness obtained in the following measurement 2, i.e., L1.n-L2.n, is calculated at 100 measurement points, and the "brightness difference deviation 3σ" calculated from the brightness difference at the 100 measurement points is 100 or more, Measurement 1 A first measurement sample is prepared in which a first polarizer, an optical biaxially stretched plastic film, and a second polarizer are arranged in this order on a surface light source. In the first measurement sample, the direction of the slow axis of the optical biaxially stretched plastic film is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer, and the absorption axis of the second polarizer is arranged to be approximately perpendicular to the direction of the absorption axis of the first polarizer. The surface light source of the first measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at measurement points of 100×100 set at equal intervals in the vertical and horizontal directions in an arbitrary first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L1.1, the brightness of the 100th measurement point is defined as L1.100, and the brightness of the nth measurement point is defined as L1.n, Measurement 2 A second measurement sample is prepared in which the first polarizer and the second polarizer are arranged in this order on the same surface light source as the measurement 1, wherein in the second measurement sample, the absorption axis of the second polarizer is arranged to be approximately perpendicular to the absorption axis of the first polarizer. The surface light source of the second measurement sample is made to display white, and the brightness of the transmitted light emitted from the second polarizer side is measured at 100×100 measurement points set at equal intervals in the vertical and horizontal directions in an area substantially consistent with the first area, and 100 points in an arbitrary horizontal column are extracted from the measurement results, and are sequentially used as the first measurement point to the 100th measurement point, and the brightness of the first measurement point is defined as L2.1, the brightness of the 100th measurement point is defined as L2.100, and the brightness of the nth measurement point is defined as L2.n; Condition 2 The in-plane phase difference Re is 2500 nm or less.
Citation Information
Patent Citations
Visibility improving method of liquid crystal display device, and liquid crystal display device using the same
JP2011107198A